Cathode for hydrogen generation, cathode for alkaline water electrolysis, method for manufacturing the cathode, bipolar electrolytic cell, electrolytic cell for alkaline water electrolysis, and method for producing hydrogen
By using multi-layer catalytic layers of Pt and Sc or Y in the alkaline hydrolytic electrolytic cathode, the problems of energy conversion efficiency decline and overvoltage rise caused by renewable energy power fluctuations are solved, and efficient and stable energy conversion is achieved.
Patent Information
- Application Number
- JP2023122884
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-06
AI Technical Summary
In the prior art, the cathode used for alkaline hydrolysis electrolysis is difficult to maintain high energy conversion efficiency when facing unstable power supply of renewable energy, and catalytic layer loss and overvoltage increase due to reverse current.
Using a catalytic layer containing Pt and an oxide/hydroxide selected from Sc or Y, the molar ratio of Pt to element R is controlled between 95:5 and 65:35, and through a multi-layer structure design, the electrical double layer capacitance and conductivity are improved, and the adhesion between the catalytic layer and the substrate is enhanced.
Under renewable energy power fluctuations, the cathode can maintain high energy conversion efficiency for a long time, reduce overvoltage rise, improve reverse current durability, and avoid catalytic layer peeling and corrosion.
Smart Images

Figure 2025018833000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cathode for hydrogen generation, a cathode for alkaline water electrolysis, a method for producing a cathode, a bipolar electrolytic cell, an electrolytic cell for alkaline water electrolysis, and a method for producing hydrogen. [Background technology]
[0002] 2. Description of the Related Art In recent years, in order to solve problems such as global warming caused by greenhouse gases such as carbon dioxide and dwindling reserves of fossil fuels, technologies that utilize renewable energy, such as wind power generation and solar power generation, have been attracting attention.
[0003] Renewable energy output is highly variable because it depends on weather conditions. As a result, it is not always possible to transport the electricity generated by renewable energy sources to the general power grid, and there are concerns about the social impacts of this, such as an imbalance in power supply and demand and instability in the power grid.
[0004] Therefore, research is being conducted into converting electricity generated from renewable energy sources into a form that can be stored and transported, and using this electricity.Specifically, studies are being conducted into the generation of storable and transportable hydrogen through the electrolysis of water using electricity generated from renewable energy, and the use of hydrogen as an energy source or raw material.
[0005] Hydrogen is widely used industrially in oil refining, chemical synthesis, metal refining, etc., and in recent years, the possibility of its use is expanding in hydrogen stations for fuel cell vehicles (FCVs), smart communities, hydrogen power plants, etc. For this reason, there are high expectations for the development of technology to obtain hydrogen, especially from renewable energy sources.
[0006] Methods for electrolyzing water include solid polymer water electrolysis, high-temperature steam electrolysis, and alkaline water electrolysis. Among these, alkaline water electrolysis is considered to be one of the most promising methods because it has been industrialized for several decades, it can be carried out on a large scale, and it is inexpensive compared to other water electrolysis devices.
[0007] However, in order to adapt alkaline water electrolysis as a means for storing and transporting energy in the future, it is necessary to enable water electrolysis by efficiently and stably utilizing electric power, which has large output fluctuations as described above, and there is a demand to solve various issues related to electrolytic cells and devices for alkaline water electrolysis.
[0008] It is well known that in order to solve the problem of reducing the electrolysis voltage in alkaline water electrolysis and improving the power consumption rate of hydrogen production, it is effective to adopt, as the structure of the electrolysis cell, a structure called a zero-gap structure, in which the gap between the diaphragm and the electrodes is substantially eliminated (see Patent Documents 1 and 2). In the zero-gap structure, the generated gas is quickly released to the side opposite the diaphragm of the electrode through the pores of the electrode, thereby reducing the distance between the electrodes and minimizing the occurrence of gas accumulation near the electrodes, thereby reducing the electrolysis voltage. The zero-gap structure is extremely effective in reducing the electrolysis voltage, and is adopted in various electrolysis devices. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Patent No. 5553605 [Patent Document 2] International Publication No. 2015 / 098058 Summary of the Invention [Problem to be solved by the invention]
[0010] However, the conventional cathodes for alkaline water electrolysis described in Patent Documents 1 and 2 had a problem in that the catalyst layer was depleted or fell off due to repeated application of a forward current that advances the intended electrolytic reaction and a reverse current (reverse current) that occurs after the forward current is stopped, resulting in an increase in overvoltage. Therefore, with a variable power source such as renewable energy, it was difficult to maintain high energy conversion efficiency over a long period of time.
[0011] Therefore, an object of the present invention is to provide a cathode that maintains high energy conversion efficiency for a long period of time without increasing overvoltage even when hydrogen generation is repeatedly started and stopped. [Means for solving the problem]
[0012] That is, the present invention is as follows. (1) At least one of Pt, Pt oxide, and Pt hydroxide on a surface of a conductive substrate; At least one of a metal, an oxide, and a hydroxide of an element R selected from Sc or Y; A cathode for generating hydrogen having a catalyst layer containing A cathode for generating hydrogen, characterized in that the molar ratio of Pt element to element R (Pt:element R) in the catalyst layer is 95:5 to 65:35. (2) The cathode according to claim 1, which is a cathode for alkaline water electrolysis. (3) The cathode according to (1) or (2), wherein the catalyst layer contains the same type of element as that contained in the conductive base material. (4) The cathode according to any one of (1) to (3), characterized in that the catalytic layer comprises a first layer formed on the surface of the conductive base material and a second layer formed on the first layer, the first layer having a different molar ratio between Pt element and R element. (5) The cathode according to (4), wherein the molar ratio of the element R in the second layer is greater than the molar ratio of the element R in the first layer. (6) The cathode according to (4) or (5), wherein the first layer contains the same type of element as that contained in the conductive base material. (7) The cathode according to any one of (1) to (6), characterized in that, when a peak area of an X-ray diffracted by a (111) plane of a Pt metal in the catalytic layer is IPt, and a peak area of an X-ray diffracted by a (200) plane and a (111) plane of PtO is IPtO, a value of [IPt / (IPt+IPtO)] is 0.1 or more. (8) The cathode according to any one of (1) to (7), wherein the element R is Y. (9) The cathode according to any one of (1) to (8), wherein the conductive base material contains Ni. (10) The cathode according to (9), wherein the conductive base material is a plain weave mesh made of Ni fine wires having a wire diameter of 0.05 mm or more and 1.00 mm or less woven at 20 mesh or more and 60 mesh or less. (11) The cathode according to (9), wherein the conductive base material is a Ni foil having a thickness of 100 μm or less. (12) The cathode according to any one of (9) to (11), wherein the catalyst layer contains Pt, Y and Ni. (13) The cathode according to (12), wherein the catalyst layer comprises the first layer containing Pt and Ni, and the second layer containing Pt and Y. (14) The loading amount of the catalyst layer is 4.5 g / m 2 More than 20g / m 2 The cathode according to any one of (1) to (13), characterized in that: (15) The amount of Pt element supported in the catalyst layer is 3.5 g / m 2 More than 15g / m 2 The cathode according to any one of (1) to (14), characterized in that: (16) The cathode according to any one of (1) to (15), wherein the catalytic layer contains a hydrogen storage alloy. (17) The cathode according to (16), wherein the hydrogen storage alloy contains Pd. (18) 6kA / m 2 After applying a reduction current of 15A / m for 1 hour 2 The cumulative discharge amount until the potential reaches +1.12V (vs. RHE) is 1500C / m 2 More than 10000C / m 2 The cathode according to any one of (1) to (17), characterized in that: (19) Electric double layer capacitance is 0.01 F / cm 2 More than 0.15F / cm 2The cathode according to any one of (1) to (18), characterized in that: (20) A coating step of coating the conductive base material with a coating liquid containing at least a Pt compound and a compound containing an element R; a precursor layer forming step of drying the coating liquid to form a precursor layer containing Pt and an element R on the conductive base material; A calcination step of heating the precursor layer in a temperature range of 300°C to 800°C to obtain a catalyst layer. A method for producing a cathode according to the present invention, comprising steps of repeating the steps in sequence two or more times. (21) A first coating step of coating the conductive base material containing Ni with a first coating liquid containing at least a Pt compound and Ni; a first precursor layer forming step of drying the first coating liquid to form a first precursor layer containing Pt and Ni on the conductive base material; a first firing step of heating the first precursor layer in a temperature range of 300° C. to 800° C. to obtain the first layer; After the first step, which is repeated two or more times in sequence, a second coating step of coating a second coating liquid containing at least a Pt compound and a Y compound on the conductive base material on which the first layer has been formed; a second precursor layer forming step of drying the second coating liquid to form a second precursor layer containing Pt and Y on the first coating layer; A second firing step of heating the second precursor layer at a temperature in the range of 300° C. to 800° C. to obtain a second layer. The method for producing a cathode according to (4), further comprising repeating the second step two or more times in sequence. (22) A first coating step of coating the conductive base material containing Ni with a first coating liquid containing at least a Pt compound and Ni; a first precursor layer forming step of drying the first coating liquid to form a first precursor layer containing Pt and Ni on the conductive base material; a first firing step of heating the first precursor layer in a temperature range of 300° C. to 800° C. to obtain the first layer; After the first step, which is repeated two or more times in sequence, a second coating step of coating a second coating liquid containing at least a Pt compound and a Y compound on the conductive base material on which the first layer has been formed; a second precursor layer forming step of drying the second coating liquid to form a second precursor layer containing Pt and Y on the first coating layer; A second firing step of heating the second precursor layer at a temperature in the range of 300° C. to 800° C. to obtain a second layer. The method for producing a cathode according to (13), further comprising repeating the second step two or more times in sequence. (23) A bipolar electrolytic cell comprising the cathode according to the present invention. (24) A gas-storage device comprising the cathode and an anode, 6kA / m 2 After passing an oxidation current of 15A / m for 1 hour, 2 The cumulative discharge amount until the potential reaches +0.12V (vs. RHE) is 6kA / m 2 After applying a reduction current of 15A / m for 1 hour 2 The bipolar electrolytic cell according to (23), wherein the cumulative discharge amount is greater than an accumulated discharge amount until the potential reaches +1.12 V (vs. RHE) when an oxidation current of +1.0 V is passed through the bipolar electrolytic cell. (25) 6 kA / m 2 After passing an oxidation current of 15A / m for 1 hour, 2 The cumulative discharge amount until the potential reaches +0.12V (vs. RHE) is 10,000C / m 2 More than 300000C / m 2 A bipolar electrolytic cell according to (24), characterized in that: (26) The bipolar electrolytic cell according to claim 25, wherein the anode contains Ni. (27) 3 to 200 bipolar electrolytic cells according to the present invention; at least one cathode terminal cell; at least one anode terminal cell; An electrolytic cell for alkaline water electrolysis comprising: (28) A method for producing hydrogen, comprising electrolyzing alkali-containing water using the alkaline water electrolysis cell according to the present invention to produce hydrogen. (29) A method for producing hydrogen, comprising electrolyzing alkali-containing water using the alkaline water electrolysis cell according to (27) to produce hydrogen. (30) A method for producing hydrogen according to (29), characterized in that hydrogen is produced by electrolyzing water containing an alkali using a variable power source that involves repeating positive current application and cessation of positive current application. Effect of the Invention
[0013] According to the present invention, it is possible to provide a cathode that maintains high energy conversion efficiency for a long period of time without an increase in overvoltage even when hydrogen generation is repeatedly started and stopped. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a side view illustrating an example of an entire electrolytic cell for alkaline water electrolysis including a bipolar electrolytic cell according to the present embodiment. [Diagram 2] FIG. 2 is a diagram showing a cross section of the inside of an electrolytic cell of an alkaline water electrolysis cell including the bipolar electrolytic cell of the present embodiment, the electrolytic cell being enclosed in a dashed rectangular frame in FIG. 1 . [Diagram 3] FIG. 1 is a diagram showing an outline of an electrolysis device used in Examples and Comparative Examples. [Figure 4] FIG. 1 is a diagram showing an outline of an alkaline water electrolysis cell used in an electrolysis test. [Diagram 5] FIG. 5 is a diagram showing a cross section of the inside of an electrolysis cell of an alkaline water electrolysis cell used in an electrolysis test, the electrolysis cell being a portion of a dashed-dotted rectangular frame X in FIG. 4. [Figure 6] FIG. 5 is a diagram showing a cross section of the inside of an electrolysis cell of an alkaline water electrolysis cell used in an electrolysis test, the electrolysis cell being a part of a rectangular frame Y enclosed by a two-dot dashed line in FIG. 4. [Figure 7] FIG. 1 is a diagram showing an example of discharge curves of a cathode and an anode of an example obtained in an electrolysis test. [Figure 8]FIG. 13 is a diagram showing the results of cyclic voltammetry of the cathode of the example obtained in an electrolysis test. [Figure 9] FIG. 13 is a diagram showing the results of cyclic voltammetry of a cathode of a comparative example obtained in an electrolysis test. [Figure 10] FIG. 13 is a diagram showing a spectrum obtained by X-ray photoelectron spectroscopy measurement of a cathode of a comparative example obtained in an electrolysis test. [Figure 11] FIG. 13 is a diagram showing an SEM observation image of a cathode of a comparative example obtained in an electrolysis test. [Figure 12] FIG. 2 is a diagram showing a discharge curve of a cathode, a discharge curve of an anode, and a final potential. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. It should be noted that the present embodiment is merely an example for explaining the present invention, and the present invention is not limited to the embodiment. In other words, the present invention can be modified in various ways without departing from the gist of the present invention.
[0016] <Cathode for hydrogen generation, cathode for alkaline water electrolysis> The cathode of this embodiment is a cathode for hydrogen generation and a cathode for alkaline water electrolysis, which has a catalyst layer on the surface of a conductive substrate. In hydrogen production by alkaline water electrolysis, reducing energy consumption, specifically the electrolysis voltage, is a major issue. Since the electrolysis voltage is highly dependent on the hydrogen generation overpotential of the cathode, the performance of the cathode is important.
[0017] The electrolysis voltage for alkaline water electrolysis is divided into the theoretically required voltage for water electrolysis, the overvoltage for the anode reaction (oxygen generation), the overvoltage for the cathode reaction (hydrogen generation), and the voltage due to the distance between the anode and cathode. Here, overvoltage refers to the voltage that must be applied in excess of the theoretical decomposition voltage when a certain current is passed, and its value depends on the current value. In other words, by using electrodes with a low overvoltage, it is possible to reduce the power consumption to produce the same amount of hydrogen.
[0018] Furthermore, the cathode of the present embodiment has an improved reverse current durability, and thus has an effect of being able to maintain a low overvoltage for a long period of time. In addition, even when an unstable current such as that from renewable energy is used, corrosion of the cathode base material and catalytic layer, detachment of the catalytic layer, dissolution in the electrolyte, adhesion of inclusions to the diaphragm, and the like are unlikely to occur.
[0019] In order to realize a low overvoltage, the cathode must have high electrical conductivity, high hydrogen generation ability, high wettability of the electrode surface with the electrolyte, etc. The cathode of the present embodiment contains a metal element such as Pt, so that it is possible to satisfy these requirements.
[0020] In one embodiment, the cathode has a catalyst layer on the surface of a conductive substrate, the catalyst layer containing at least one of Pt, Pt oxide, and Pt hydroxide (hereinafter, these may be collectively referred to as a "Pt-based compound"), and at least one of a metal, oxide, and hydroxide of an element R selected from Sc and Y (hereinafter, these may be collectively referred to as an "element R-based compound"). As described above, by containing a Pt-based compound in the catalyst layer, the hydrogen generation overvoltage of the cathode can be reduced. Furthermore, by containing a compound capable of increasing the electric double layer capacity, which is an index of the effective area used for electrolysis on the surface of the cathode, in the catalyst layer, the overvoltage can be further reduced. In order to maintain the effect of increasing the electric double layer capacity for a long period of time, it is necessary that the element does not dissolve in the electrolyte in the electrolysis environment, so it is preferable that the element is electrochemically stable as a solid. Furthermore, it is preferable that the element does not undergo a valence change due to electrochemical oxidation-reduction even when repeatedly exposed to reduction associated with forward current and oxidation associated with reverse current caused by the cessation of forward current. If a valence change occurs, the crystal form will change every time forward current is applied and the cessation of forward current is applied, and repeating this causes physical collapse of the catalyst layer, inducing an increase in overvoltage. As a result of thorough investigations conducted from these perspectives, it was found that in order to maintain high energy conversion efficiency over the long term without an increase in overvoltage, even when hydrogen generation is repeatedly started and stopped, it is preferable for the catalyst layer to contain an element R selected from Sc and Y, which are trivalent ions and electrochemically stable within the potential window of water from pH 7 to pH 16. For information on the electrochemical stability of each element within the potential window of water from pH 7 to pH 16, reference was made to Atlas of Electrochemical Equilibria in Aqueous Solutions (by Marcel Pourbaix, published by the National Association of Corrosion Engineers, 1974). That is, by further containing an R-based compound selected from Sc and Y in the catalyst layer in addition to the Pt-based compound described above, deterioration of the cathode can be suppressed and high energy conversion efficiency can be maintained even when the electrolytic cell is operated under a variable power supply.
[0021] In the cathode of this embodiment, the molar ratio of Pt element to element R (Pt:R) in the catalyst layer is 95:5 to 65:35, preferably 90:10 to 70:30, and more preferably 85:15 to 73:27. The more the R-based compound, the higher the electric double layer capacity, and the more effective it is in reducing hydrogen generation overvoltage and improving reverse current durability. On the other hand, since the R-based compound, particularly oxides and hydroxides, has low electrical conductivity, if there is too much, it inhibits the electrical conductivity of the catalyst layer and increases the overvoltage. Therefore, in this embodiment, by setting the molar ratio of Pt element to element R in the catalyst layer within the above range, the cathode overvoltage can be kept even lower even when the electrolytic cell is operated under a variable power supply, and it becomes possible to maintain a high energy conversion efficiency for a long period of time.
[0022] In addition, it is preferable that the catalyst layer contains the same type of element as that contained in the conductive base material, because the affinity between the catalyst layer and the conductive base material is improved, which suppresses the catalyst layer from falling off from the base material and increases the reverse current durability.
[0023] The catalyst layer may have a laminated structure including a first layer formed on the surface of the conductive base material and a second layer formed on the first layer, the first layer having a different molar ratio between Pt and R.
[0024] In the case of a laminated structure, the catalytic layer is composed of a first layer formed on the surface of the conductive base material and a second layer formed on the first layer, and it is preferable that the molar ratio of element R in the second layer is greater than the molar ratio of element R in the first layer. This is because adding element R to the second layer closer to the surface of the catalytic layer results in more element R contributing to electrolysis than adding element R to the first layer, thereby increasing reverse current durability.
[0025] Furthermore, in the case of a laminated structure, it is preferable that the first layer contains the same type of element as that contained in the conductive base material, because the affinity between the first layer and the conductive base material is improved, which suppresses the catalyst layer from falling off from the base material and increases the reverse current durability.
[0026] In addition, when the peak area of X-rays diffracted by the (111) plane of the Pt metal in the catalytic layer is IPt, and the peak area of X-rays diffracted by the (200) and (111) planes of the Pt oxide is IPtO, the value of [IPt / (IPt+IPtO)] is preferably 0.1 or more. This is because, since Pt oxide is electrochemically reduced to metal when subjected to hydrogen generating electrolysis, a higher ratio of metal crystals from the beginning reduces morphological changes in the catalytic layer and increases durability.
[0027] The element R is not particularly limited, but is particularly preferably Y from the viewpoint of keeping the cathode overvoltage lower for a long period of time.
[0028] The material constituting the conductive base material is not particularly limited, but is preferably a transition metal from the viewpoint of achieving both electrical conductivity and durability. The transition metal is more preferably at least one selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Ru, Rh, Pd, Ag, Ir, Pt, and Au, further preferably at least one selected from the group consisting of Ni, Ti, and Fe, and particularly preferably contains at least Ni. The material of the conductive substrate may be a single transition metal, or an alloy or mixture of two or more transition metals, and may further contain, in addition to the transition metal, typical elements such as C, O, N, Si, P, and S.
[0029] The cathode of this embodiment is preferably a porous body in order to increase the surface area used for electrolysis and to efficiently remove gas generated by electrolysis from the electrode surface. In particular, in the case of a zero gap electrolytic cell, it is necessary to degas the gas generated from the back side of the contact surface with the diaphragm, so that the surface of the cathode opposite to the surface in contact with the membrane is preferably perforated. From this viewpoint, the form of the conductive substrate is not particularly limited, but it is preferable that the conductive substrate has holes through which air bubbles can pass, such as punched metal, expanded metal, punched foil, mesh woven with metal wires, foamed metal, sintered metal, metal fiber, and metal paper.
[0030] In addition, the effect of improving the reverse charge resistance described above is enhanced when the conductive substrate has a configuration that does not have corners or protrusions, because the presence of corners or protrusions can become the starting point for interfacial peeling between the catalyst layer and the substrate. Therefore, the conductive substrate is preferably a mesh made of metal wires that has no corners or protrusions, that is, a cross section perpendicular to the axial direction that is circular or elliptical. If the conductive substrate has corners or protrusions, such as expanded metal, the corners or protrusions can become starting points for interfacial peeling of the catalyst layer, which may weaken the effect of improving reverse current durability of the present invention.
[0031] When a plain weave mesh is used for the conductive substrate, the dimensions are not particularly limited, but in order to increase the electrolytic reaction field by increasing the electrolytic surface area and to efficiently remove the gas generated by electrolysis from the electrode surface, the wire diameter is preferably 0.05 mm to 1.0 mm and the pitch is preferably 20 mesh to 60 mesh, and more preferably 0.1 mm to 0.3 mm and the pitch is more preferably 30 mesh to 50 mesh.
[0032] When a foil is used as the conductive base material, the dimensions are not particularly limited, but it is desirable for the foil to have flexibility in order to further enhance the effect of improving electrolysis efficiency by the zero gap structure, and the foil thickness is preferably 100 μm or less, more preferably 60 μm or less, and even more preferably 40 μm or less.
[0033] Furthermore, the loading amount of the catalyst layer is 4.5 g / m 2 More than 20g / m 2 Preferably, the thickness is 5.0 g / m or less. 2 More than 15g / m 2 More preferably, it is 6.0 g / m or less. 2More than 10g / m 2 It is more preferable that the loading amount of the catalyst layer is 4.5 g / m or less. 2 By setting the amount of the catalyst layer to 20 g / m or more, it is possible to reduce the overvoltage and increase the durability against reverse current. 2 This is because, by setting the thickness to be equal to or less than this range, it is possible to suppress peeling of the catalyst layer due to a decrease in the mechanical strength of the catalyst layer and an increase in overvoltage due to a decrease in the electrical conductivity of the catalyst layer.
[0034] Furthermore, the catalyst layer contains Pt element and element R, and preferably contains Pt, and element R is Y and Ni. When the catalyst layer has a laminated structure, it is more preferable that the catalyst layer is composed of the first layer containing Pt and Ni and the second layer containing Pt and Y.
[0035] Furthermore, the amount of Pt element supported in the catalyst layer is 3.5 g / m 2 More than 15g / m 2 Preferably, the thickness is 4.0 g / m or less. 2 More than 10g / m 2 More preferably, it is 5.0 g / m or less. 2 More than 7.0g / m 2 It is more preferable that the amount of Pt element supported in the catalyst layer is 3.5 g / m or less. 2 By setting the amount of Pt element supported in the catalyst layer at 15 g / m or more, it is possible to reduce the overvoltage and increase the reverse current durability. 2 This is because, by setting the thickness to be equal to or less than this range, it is possible to suppress peeling of the catalyst layer due to a decrease in the mechanical strength of the catalyst layer and an increase in overvoltage due to a decrease in the electrical conductivity of the catalyst layer.
[0036] In addition, the average thickness of the catalyst layer is not particularly limited, but is preferably 0.30 μm or more. By setting the average thickness of the catalyst layer to 0.30 μm or more, cracks in the catalyst layer perpendicular to the conductive substrate are reduced, the surface area of the conductive substrate in contact with the electrolyte is reduced, and peeling of the catalyst layer caused by oxidation-reduction due to reverse charging at the interface between the catalyst layer and the conductive substrate can be suppressed. On the other hand, if the average thickness of the catalyst layer is too large, the mechanical strength decreases and the catalyst layer becomes physically prone to peeling off, so the average thickness of the catalyst layer is preferably 10 μm or less. From the same viewpoint, the average thickness of the catalyst layer is more preferably 0.5 μm or more and 5 μm or less, and further preferably 0.7 μm or more and 4 μm or less.
[0037] Moreover, it is more preferable that the catalyst layer contains a hydrogen storage alloy. By containing a hydrogen storage alloy, hydrogen generated by electrolysis is retained as atomic hydrogen in the catalyst layer. The reducing power of this atomic hydrogen promotes the reduction of the substrate oxide layer caused by forward current flow and inhibits the growth of the substrate oxide layer caused by reverse current flow, thereby inhibiting morphological changes due to oxidation and reduction of the substrate and improving reverse current durability.
[0038] The hydrogen storage alloy is not particularly limited, but is preferably Pd in view of electrochemical stability.
[0039] In addition, the cathode of this embodiment has a current density of 6 kA / m 2 After applying a reduction current of 15A / m for 1 hour 2 The cumulative discharge amount until the potential reaches +1.12V (vs. RHE) is 1500C / m 2 More than 10000C / m 2 When the accumulated discharge amount is within the above range, the rate at which the potential of the cathode becomes noble due to the reverse current is slowed down, and the potential change stress on the cathode and the deterioration associated therewith can be reduced.
[0040] The effective area of the cathode surface used for electrolysis can be determined in a pseudo manner by measuring the capacity of the electric double layer formed at the interface between the cathode and the electrolyte. The electric double layer capacity can be measured by, for example, electrochemical impedance method or cyclic voltammetry method. In the former, the electric double layer capacity is calculated by analyzing a Cole-Cole plot obtained by plotting the real part and the imaginary part obtained by AC impedance measurement, by equivalent circuit fitting. In the latter, cyclic voltammetry is measured at several levels of potential sweep speed in a potential region where no faradaic current is generated at the cathode, and the non-faradaic current value at a certain potential obtained against the sweep speed is plotted, and the electric double layer capacity is calculated from the slope.
[0041] In the cathode of this embodiment, from the viewpoint of increasing the effective area used for electrolysis and reducing the hydrogen generation overvoltage, the electric double layer capacity calculated by cyclic voltammetry is 0.001 F / cm 2 Furthermore, from the viewpoint of ensuring a sufficient electric double layer capacity to maintain a low overvoltage even if the catalyst is depleted or removed due to a reverse current caused by the stop of forward current application, it is preferable that the electric double layer capacity calculated by cyclic voltammetry is 0.02 F / cm or more. 2 More preferably, it is 0.03 F / cm2 or less. 2 It is particularly preferable that the resistance be not less than 0.15 F / cm2.
[0042] Furthermore, the coating resistance of the cathode in this embodiment is 2 Ω cm 2 It is preferably equal to or less than 0.5 Ω cm, and more preferably 0.5 Ω cm 2 If the cathode film resistance is too high, overvoltage increases when electrolysis is performed under high current density conditions in order to obtain high energy efficiency. The film resistance can be measured, for example, by electrochemical impedance spectroscopy. The film resistance is calculated by analyzing a Cole-Cole plot, which is a plot of the real and imaginary parts obtained by AC impedance measurement, using equivalent circuit fitting.
[0043] Examples of a method for producing the cathode by forming the catalytic layer on the conductive substrate include a plating method, a thermal spraying method such as a plasma thermal spraying method, a pyrolysis method in which a precursor layer solution is applied to the conductive substrate and then heated, a method in which a catalytic substance is mixed with a binder component and fixed to the substrate, and a vacuum film formation method such as a sputtering method.
[0044] The pyrolysis method allows a thin film of uniform thickness to be formed on a porous substrate, so that the surface of the conductive substrate can be efficiently coated with a small amount of raw material. The thermal decomposition method preferably includes a precursor layer forming step of forming a precursor layer on the surface of the conductive substrate, and a calcination step of heating the conductive substrate having the precursor layer formed on its surface to decompose the precursor layer and form a catalyst layer.
[0045] The precursor layer forming step may be, for example, a method of applying a liquid containing a metal element to the surface of the substrate and drying it. Examples of the metal element include the Pt group elements and element R described above. The form of the metal in the coating liquid is not particularly limited, and may be fine particles of metal or metal compound, or may be dissolved and ionized. In the case of fine particle state, it is preferable that the metal is dispersed in the liquid in order to form a homogeneous precursor layer. Therefore, the particle size is preferably 100 nm or less. In the case of ionization, examples of the metal salt include halide salts such as fluoride, chloride, bromide, and iodide, inorganic compound salts such as nitrate, sulfate, and phosphate, and organic compound salts represented by acetate. Among these, chloride and nitrate are preferably used because the raw materials are industrially available. Furthermore, nitrate is more preferable because the deterioration of the substrate due to the anion component remaining after decomposition is small, and an electrode with good storage stability can be obtained. The solvent of the solution may be any solvent capable of dissolving the solute, such as a metal salt. If a high-concentration solution can be prepared, the amount of coating can be increased, and productivity can be improved. Therefore, it is preferable that the solution contains at least one of water or an alcohol having 2 to 5 carbon atoms. If the concentration of the metal salt in the solution is low, a lot of energy is required to volatilize the solvent. On the other hand, if the concentration of the metal salt is high, unevenness may occur, and the thickness of the catalyst layer may become non-uniform. Therefore, the concentration of the metal salt in the coating solution used in the precursor formation step is preferably 0.001 mol / L or more and 1 mol / L or less, more preferably 0.01 mol / L or more and 0.5 mol / L.
[0046] In the precursor layer forming step, the liquid containing a metal element can be applied to the conductive substrate surface by various known methods. For example, the dip method of immersing the substrate in the liquid, the method of applying the liquid to the substrate with a brush, the roll method of applying the liquid impregnated in a sponge-like roll to the substrate, and the electrostatic application method of charging the coating liquid and the substrate with opposite charges and spraying the coating liquid using a spray or the like can be used. In particular, the roll method and the electrostatic application method are preferably used from the viewpoint of productivity and the viewpoint of uniform application of the catalyst layer. The conductive substrate may be subjected to a surface treatment to provide irregularities on the surface prior to application of the solution. Providing irregularities on the substrate surface improves adhesion between the substrate and the catalyst layer. The method of surface treatment is not particularly limited, and examples include blasting and etching using a chemical solution.
[0047] The temperature for forming the catalyst layer in the firing step may be equal to or higher than the thermal decomposition temperature of the metal salt used, but is preferably equal to or higher than 300°C. This is because the thermal decomposition of many metal salts proceeds at 300°C or higher. In order to allow the thermal decomposition to proceed smoothly and remove unreacted substances, the temperature is preferably equal to or higher than 400°C, more preferably equal to or higher than 500°C. If firing is performed at a temperature higher than 800°C, the substrate may soften and deform, so the temperature is preferably equal to or lower than 800°C, more preferably equal to or lower than 600°C.
[0048] It is preferable to repeat the precursor layer forming step and the calcination step several times. In order to form a catalyst layer of a desired thickness, the amount of liquid applied each time or the concentration of the metal salt in the liquid can be adjusted, but if the amount of liquid applied each time or the metal concentration in the liquid is too high, there is a risk of unevenness, and each layer may not be formed uniformly. Therefore, by repeating the precursor layer forming step and the calcination step several times, a more uniform catalyst layer can be formed with a desired thickness. The number of repetitions is not particularly limited as long as the desired thickness is obtained, but it is preferable that it is 5 times or more.
[0049] After repeating the precursor layer forming step and the firing step multiple times, a step of firing at a temperature higher than or equal to the temperature of the firing step may be further included. The upper limit of the firing temperature in this case is preferably 800° C. or lower, more preferably 600° C. or lower.
[0050] In this embodiment, the above-mentioned features of the cathode for hydrogen generation and the cathode for alkaline water electrolysis may be used alone or in combination.
[0051] <Cathode manufacturing method> The method for producing the cathode of the present embodiment is not particularly limited. For example, the cathode can be produced by the following production method. a coating step of coating the conductive base material with a coating liquid containing at least a Pt compound and a compound of element R; a precursor layer forming step of drying the coating liquid to form a precursor layer containing Pt and an element R on the conductive base material; A calcination step of heating the precursor layer in a temperature range of 300°C to 800°C to obtain a catalyst layer. Repeating the steps in sequence two or more times; A method for producing a cathode having the above structure.
[0052] As a method for producing the cathode of this embodiment, the following production method can also be used. a first coating step of coating the conductive base material with a first coating liquid containing at least a Pt compound and a compound of element R; a first precursor layer forming step of drying the first coating liquid to form a first precursor layer containing Pt and an element R on the conductive base material; a first firing step of heating the first precursor layer in a temperature range of 300° C. to 800° C. to obtain the first layer; After the first step, which is repeated two or more times in sequence, a second coating step of coating a second coating liquid containing at least a Pt compound and a compound of element R in a molar ratio different from that of the first layer on the conductive base material on which the first layer is formed; a second precursor layer forming step of drying the second coating liquid to form a second precursor layer on the first layer, the second precursor layer containing Pt and the element R in a molar ratio different from that of the first layer; A second firing step of heating the second precursor layer at a temperature in the range of 300° C. to 800° C. to obtain a second layer. A method for producing a cathode comprising repeating the second step two or more times in sequence.
[0053] Furthermore, the cathode of this embodiment can also be manufactured by the following manufacturing method. A first coating step of coating the conductive base material containing Ni with a first coating liquid containing at least a Pt compound and Ni; a first precursor layer forming step of drying the first coating liquid to form a first precursor layer containing Pt and Ni on the conductive base material; a first firing step of heating the first precursor layer in a temperature range of 300° C. to 800° C. to obtain the first layer; After the first step, which is repeated two or more times in sequence, a second coating step of coating a second coating liquid containing at least a Pt compound and a compound of element R on the conductive base material on which the first layer has been formed; a second precursor layer forming step of drying the second coating liquid to form a second precursor layer containing Pt and an element R on the first layer; A second firing step of heating the second precursor layer at a temperature in the range of 300° C. to 800° C. to obtain a second layer. A method for producing a cathode comprising repeating the second step two or more times in sequence.
[0054] <Bipolar electrolytic cell, alkaline water electrolysis cell> The bipolar electrolytic cell of this embodiment is characterized by including the cathode of this embodiment described above. By providing the cathode of this embodiment, even when hydrogen generation is repeatedly started and stopped, the overvoltage does not increase and high energy conversion efficiency can be maintained for a long period of time.
[0055] The alkaline water electrolysis cell of this embodiment includes 3 to 200 bipolar electrolytic cells of this embodiment, at least one cathode terminal cell, and at least one anode terminal cell. By configuring an electrolytic cell from the alkaline water electrolysis cell of this embodiment, even when hydrogen generation is repeatedly started and stopped, overvoltage does not increase and high energy conversion efficiency can be maintained for a long period of time.
[0056] FIG. 1 shows an overall side view of an example of an electrolytic cell for alkaline water electrolysis including a bipolar electrolytic cell of the present embodiment. FIG. 2 shows a diagram of a zero gap structure of an example of an alkaline water electrolysis cell including the bipolar electrolytic cell of this embodiment (a cross-sectional view of the part enclosed in a dashed rectangular frame in FIG. 1). As shown in Figs. 1 and 2 , the alkaline water electrolysis cell 50 of this embodiment is preferably an alkaline water electrolysis cell in which a plurality of elements 60, each including an anode 2a, a cathode 2c, a partition wall 1 separating the anode 2a and the cathode 2c, and an outer frame 3 bordering the partition wall 1, are stacked with a diaphragm 4 interposed therebetween.
[0057] In the alkaline water electrolysis cell 50 of this embodiment, the diaphragm 4 is in contact with the anode 2a and the cathode 2c to form a zero gap structure Z (see FIG. 2).
[0058] The alkaline water electrolysis cell of the present embodiment may be of a monopolar type or a bipolar type, and is preferably an alkaline water electrolysis cell in which bipolar elements are stacked via a diaphragm. The monopolar type is a method in which one or more elements are each directly connected to a power source, while the bipolar type is a method in which multiple bipolar elements are arranged in series and the elements at both ends are connected to a power source.
[0059] In this embodiment, as shown in FIG. 1, an alkaline water electrolysis cell 50 is configured by stacking a required number of bipolar elements 60. In the example shown in FIG. 1 , the alkaline water electrolysis cell 50 includes a fast head 51g, an insulating plate 51i, and an anode terminal element 51a arranged in this order from one end, and further includes an anode side gasket portion, a diaphragm 4, a cathode side gasket portion, and a bipolar element 60 arranged in this order. At this time, the bipolar element 60 is arranged so that the cathode 2c faces the anode terminal element 51a side. The anode gasket to the bipolar element 60 are arranged repeatedly as many times as necessary for the designed production volume. After the anode gasket to the bipolar element 60 are arranged repeatedly as necessary, the anode side gasket portion, the diaphragm 4, and the cathode side gasket portion are arranged again, and finally the cathode terminal element 51c, the insulating plate 51i, and the loose head 51g are arranged in this order. The alkaline water electrolysis cell 50 is integrated by tightening the entire cell with tie rods 51r to form the alkaline water electrolysis cell 50. The arrangement of the alkaline water electrolysis cell 50 can be arbitrarily selected from either the anode side or the cathode side, and is not limited to the above-mentioned order.
[0060] As shown in FIG. 1, in an alkaline water electrolysis cell 50, a bipolar element 60 is disposed between an anode terminal element 51a and a cathode terminal element 51c, and diaphragms 4 are disposed between the anode terminal element 51a and the bipolar element 60, between adjacent bipolar elements 60, and between the bipolar element 60 and the cathode terminal element 51c.
[0061] In the alkaline water electrolysis cell 50 of this embodiment, as shown in FIG. 2, the diaphragm 4 is in contact with the anode 2a and the cathode 2c to form a zero gap structure Z. In this embodiment, in particular, the portion between the partition walls 1 between two adjacent bipolar elements 60 and the portion between the partition walls 1 between an adjacent bipolar element 60 and a terminal element in the alkaline water electrolysis cell 50 are referred to as an electrolytic cell 65. The electrolytic cell 65 includes the partition wall 1, anode chamber 5a, anode 2a, and diaphragm 4 of one element, and the cathode 2c, cathode chamber 5c, and partition wall 1 of the other element.
[0062] In alkaline water electrolysis, if there is a gap between the diaphragm 4 and the anode 2a or the cathode 2c, a large amount of gas bubbles generated during electrolysis will accumulate in this portion in addition to the electrolyte, resulting in a very high electrical resistance. In order to significantly reduce the electrolysis voltage in the electrolytic cell 65, it is effective to reduce the distance between the anode 2a and the cathode 2c (hereinafter also referred to as the "electrode distance") as much as possible to eliminate the influence of the electrolyte and gas bubbles present between the anode 2a and the cathode 2c.
[0063] Thus, a zero gap structure is adopted, which can maintain a state in which the anode 2a and the diaphragm 4 are in contact with each other and the cathode 2c and the diaphragm 4 are in contact with each other over the entire electrode surface, or a state in which the inter-electrode distance is approximately the same as the thickness of the diaphragm 4 and there is almost no gap between the anode 2a and the diaphragm 4 and between the cathode 2c and the diaphragm 4 over the entire electrode surface.
[0064] In the alkaline water electrolysis cell 50 of this embodiment, as shown in FIG. 2, the partition wall 1, the outer frame 3, and the diaphragm 4 define an electrode chamber 5 through which the electrolyte passes. Representative examples of the arrangement of a header pipe, which is a pipe for distributing or collecting the electrolytic solution and is attached to the alkaline water electrolysis cell 50 shown in Figs. 1 and 2, include an internal header type and an external header type; however, either type may be adopted in the present invention, and there is no particular limitation thereon.
[0065] The components of the bipolar electrolytic cell and the alkaline water electrolysis cell of this embodiment will be described in detail below. In addition, preferred embodiments for enhancing the effects of the present invention will be described in detail below.
[0066] (bulkhead) The partition wall 1 is preferably provided between the cathode 2c and the anode 2a, between the anode 2a and the cathode current collector 2r and / or between the cathode 2c and the anode current collector 2r. The shape of the partition wall in this embodiment may be a plate shape having a predetermined thickness, but is not particularly limited. The shape of the partition wall in plan view is not particularly limited and may be rectangular (square, oblong, etc.) or circular (circle, ellipse, etc.), and here the rectangle may have rounded corners.
[0067] The size of the partition wall is not particularly limited and may be appropriately designed depending on the size of the electrode chamber. As the material for the partition wall, from the viewpoint of realizing a uniform supply of power, a material having high electrical conductivity is preferable, and from the viewpoints of alkali resistance and heat resistance, nickel, a nickel alloy, mild steel, or a nickel alloy plated with nickel is preferable.
[0068] (electrode) The size of the electrodes is not particularly limited and may be determined according to the size of the electrode chamber, and may be 0.4 m to 4.0 m in length, 0.4 m to 6.0 m in width, and 0.1 mm to 3 mm in thickness.
[0069] In the bipolar electrolytic cell of this embodiment, at least one of the anode and the cathode is preferably a porous body, and more preferably both the anode and the cathode are porous, in order to increase the surface area used for electrolysis and to efficiently remove gas generated by electrolysis from the electrode surface. In particular, in the case of a zero-gap electrolytic cell, it is necessary to degas the gas generated from the back side of the contact surface with the diaphragm, so that the surface of the electrode opposite to the surface in contact with the membrane is preferably perforated.
[0070] The anode preferably includes a porous metal body, since the catalyst layer supported on the electrode becomes porous, which increases the effective electrolysis area and allows the voltage to be reduced.
[0071] Examples of the porous body include plain weave and twill weave meshes, punched metals, expanded metals, and metal foams.
[0072] When a punched metal is used, the dimensions are not particularly limited, but in order to achieve both an increase in the amount of gas generated by an increase in the electrolysis surface area and efficient removal of the gas generated by electrolysis from the electrode surface, and from the viewpoint of mechanical strength, it is preferable that the hole diameter be 2 mm or more and 8 mm or less, the pitch be 2 mm or more and 10 mm or less, the opening ratio be 20% or more and 80% or less, and the thickness be 0.5 mm or more and 2 mm or less.
[0073] When an expanded metal is used, the dimensions are not particularly limited, but in order to achieve both an increase in the amount of gas generated by an increase in the electrolysis surface area and efficient removal of the gas generated by electrolysis from the electrode surface, and from the standpoint of mechanical strength, it is preferable that the center-to-center distance in the short direction of the mesh (SW) be 2 mm or more and 5 mm or less, the center-to-center distance in the long direction of the mesh (LW) be 3 mm or more and 10 mm or less, the thickness be 0.5 mm or more and 2 mm or less, and the opening ratio be 20% or more and 80% or less.
[0074] When a metal foam is used, the dimensions are not particularly limited, but in order to achieve both an increase in the amount of gas generated by increasing the electrolysis surface area and efficient removal of the gas generated by electrolysis from the electrode surface, and from the viewpoint of mechanical strength, it is preferable that the porosity be 80% or more and 95% or less and the thickness be 0.5 mm or more and 2.0 mm or less.
[0075] The material of the substrate is not particularly limited, but in view of resistance to the usage environment, it is preferable that the substrate contains mild steel, stainless steel, Ni, or a Ni-based alloy, and more preferably contains Ni.
[0076] The anode has holes, and in order to efficiently remove gas generated by electrolysis from the surface of the anode, it is preferable that the aperture ratio is 30% or more and 70% or less.
[0077] The catalytic layer of the anode preferably has a high oxygen generating ability, and Ni, Co, Fe, Pt group elements, etc. can be used. In order to achieve the desired activity and durability, the catalytic layer can be formed as a metal simple substance, a compound such as an oxide, a composite oxide or alloy consisting of multiple metal elements, or a mixture thereof. Specifically, Ni plating, alloy plating of Ni and Co, Ni and Fe, etc., composite oxides containing Ni and Co such as LaNiO3, LaCoO3, NiCo2O4, compounds of Pt group elements such as Ir oxide, carbon materials such as graphene, etc. can be mentioned. Organic substances such as polymers may be included to improve durability and adhesion to the substrate.
[0078] (Outer frame) The shape of the outer frame 3 in the bipolar electrolytic cell of the present embodiment is not particularly limited as long as it can frame the partition wall 1; however, the outer frame 3 may have an inner surface that is aligned in a direction perpendicular to the plane of the partition wall 1 and extends along the outer periphery of the partition wall 1. The shape of the outer frame is not particularly limited and may be determined appropriately in accordance with the shape of the partition wall in a plan view. The dimensions of the outer frame are not particularly limited and may be designed according to the outer dimensions of the electrode chamber.
[0079] The material for the outer frame is preferably a conductive material, and from the standpoint of alkali resistance and heat resistance, nickel, nickel alloy, mild steel, or nickel alloy plated with nickel is preferred.
[0080] (diaphragm) As the diaphragm 4 used in the bipolar electrolytic cell 65 of this embodiment, an ion-permeable diaphragm is used to separate the generated hydrogen gas and oxygen gas while conducting ions. As this ion-permeable diaphragm, an ion exchange membrane having ion exchange ability and a porous membrane capable of permeating the electrolytic solution can be used. As this ion-permeable diaphragm, one having low gas permeability, high ion conductivity, low electronic conductivity, and high strength is preferred.
[0081] The porous membrane has a structure that has a plurality of fine through-holes and allows the electrolyte to pass through the membrane. Since the electrolyte permeates the porous membrane to exhibit ion conduction, it is very important to control the porous structure, such as the pore size, porosity, and hydrophilicity. On the other hand, it is required to not only allow the electrolyte to pass through, but also the generated gas, that is, to have gas barrier properties. From this viewpoint, control of the porous structure is also important.
[0082] The porous membrane has a plurality of fine through-holes, and examples of the porous membrane include a polymer porous membrane, an inorganic porous membrane, a woven fabric, a nonwoven fabric, etc. These can be produced by known techniques.
[0083] Ion exchange membranes include cation exchange membranes that selectively allow cations to pass therethrough and anion exchange membranes that selectively allow anions to pass therethrough, and either type of exchange membrane can be used. The material of the ion exchange membrane is not particularly limited, and known materials can be used. For example, modified resins such as fluorine-containing resins and polystyrene-divinylbenzene copolymers can be suitably used. In particular, fluorine-containing ion exchange membranes are preferred because of their excellent heat resistance and chemical resistance.
[0084] In addition, in the zero-gap electrolytic cell 65, as a means for reducing the interelectrode distance, it is preferable to adopt a configuration in which a spring, which is an elastic body 2e, is disposed between the electrode 2 and the partition wall 1 and the electrode is supported by this spring. For example, in a first example, a spring made of a conductive material may be attached to the partition wall 1, and the electrode 2 may be attached to this spring. In a second example, a spring may be attached to the electrode rib 6 attached to the partition wall 1, and the electrode 2 may be attached to this spring. When adopting a configuration using such an elastic body, it is necessary to appropriately adjust the strength, number, shape, etc. of the spring as necessary so that the pressure at which the electrode contacts the partition membrane is not uneven.
[0085] In addition, by increasing the rigidity of the other electrode that is paired with the electrode supported via the elastic body (for example, by making the rigidity of the anode stronger than that of the cathode), the structure is designed to be less deformed even when pressed. Meanwhile, the electrode supported via the elastic body has a flexible structure that deforms when the diaphragm is pressed against it, which makes it possible to absorb unevenness caused by the tolerance in the manufacturing accuracy of the electrolytic cell and deformation of the electrodes, thereby maintaining the zero gap structure.
[0086] The zero gap structure Z may be a zero gap structure formed between the anode terminal element 51a and an element, between elements, or between an element and the cathode terminal element 51c. 2, in the bipolar electrolytic cell 65 of the present embodiment, the conductive elastic body 2e and the cathode current collector 2r are preferably provided between the cathode 2c and the partition wall 1 such that the conductive elastic body 2e is sandwiched between the cathode 2c and the cathode current collector 2r. In addition, the cathode current collector 2r is preferably in contact with the rib 6 of the cathode.
[0087] The zero gap structure Z of the bipolar electrolytic cell 65 of this embodiment preferably has a structure in which, as shown in FIG. 2 , a bipolar element 60 in which an anode rib 6 and an anode 2a are stacked in this order on the anode 2a side of the partition wall 1, and a cathode rib 6, a cathode current collector 2r, a conductive elastic body 2e, and a cathode 2c are stacked in this order on the cathode 2c side of the partition wall 1 are stacked with a diaphragm 4 sandwiched therebetween, and the diaphragm 4 is in contact with the anode 2a and the cathode 2c.
[0088] (current collector) Examples of the current collector include a cathode current collector and an anode current collector. The current collector has the role of transmitting electricity to the conductive elastic body and the electrodes laminated thereon, supporting the load received from them, and allowing the gas generated from the electrodes to pass through to the partition wall side without hindrance. Therefore, the shape of this current collector is preferably an expanded metal, a punched perforated plate, or the like. In this case, the aperture ratio of the current collector is preferably within a range in which hydrogen gas generated from the electrodes can be extracted to the partition wall side without hindrance. However, if the aperture ratio is too large, problems such as a decrease in strength or a decrease in conductivity to the conductive elastic body may occur, and if it is too small, gas escape may be poor.
[0089] As the material for the current collector, nickel, nickel alloy, stainless steel, mild steel, etc. can be used from the viewpoints of electrical conductivity and alkali resistance, but nickel, mild steel, or stainless steel-nickel alloy plated with nickel is preferable from the viewpoint of corrosion resistance.
[0090] (Conductive elastic body) The conductive elastic body is located between the current collector and the electrode, and is in contact with both the current collector and the electrode. It is essential that the conductive elastic body transmits electricity to the electrode and does not impede the diffusion of gas generated from the electrode. If gas diffusion is impeded, electrical resistance increases and the electrode area used for electrolysis decreases, resulting in a decrease in the efficiency of electrolysis. The most important role of the conductive elastic body is to evenly apply an appropriate pressure to the electrode without damaging the diaphragm, thereby tightly adhering the diaphragm to the electrode.
[0091] (electrode chamber) 2, in an alkaline water electrolysis cell 50 of this embodiment, an electrode chamber 5 through which the electrolytic solution passes is defined by a partition wall 1, an outer frame 3, and a diaphragm 4. Here, the electrode chamber 5 on the anode side across the partition wall 1 is an anode chamber 5a, and the electrode chamber 5 on the cathode side is a cathode chamber 5c.
[0092] (rib) In the bipolar electrolytic cell 65 of the present embodiment, it is preferable that the rib 6 is physically connected to the electrode 2. With such a configuration, the rib 6 serves as a support for the electrode 2, making it easy to maintain the zero gap structure Z. In addition, it is preferable that the rib 6 is electrically connected to the partition wall 1. In the above-mentioned example of the bipolar electrolytic cell, a structure is adopted in which the cathode rib-cathode current collector-conductive elastic body-cathode are stacked in this order in the cathode chamber, and a structure is adopted in which the anode rib-anode are stacked in this order in the anode chamber. However, the present invention is not limited to this, and the anode chamber may also have an "anode rib-anode current collector-conductive elastic body-anode" structure.
[0093] The material of the rib is generally a conductive metal, such as nickel-plated mild steel, stainless steel, nickel, etc. The material of the rib is preferably the same as that of the partition wall, and most preferably nickel.
[0094] (gasket) In the bipolar electrolytic cell 65 of this embodiment, as shown in FIG. 2, a gasket 7 is preferably sandwiched together with the diaphragm 4 between the outer frames 3 that border the partition walls 1. The gasket 7 is used to seal between the bipolar element 60 and the diaphragm 4 and between the bipolar elements 60 against the electrolyte and the generated gas, and can prevent leakage of the electrolyte or the generated gas to the outside of the electrolytic cell and mixing of gases between the two electrode chambers.
[0095] A typical structure of a gasket is a square or annular shape with the electrode surface hollowed out to match the surface of an element (bipolar element, anode terminal element, cathode terminal element, etc.) that contacts the frame. The diaphragm can be stacked between the elements by sandwiching it between two such gaskets. Furthermore, it is preferable that the gasket has a slit portion capable of accommodating the diaphragm so as to hold the diaphragm, and also has openings that allow the accommodated diaphragm to be exposed on both surfaces of the gasket. This allows the gasket to have a structure in which the edge of the diaphragm is accommodated in the slit portion and the end face of the edge of the diaphragm is covered. This makes it possible to more reliably prevent the electrolyte or gas from leaking from the end face of the diaphragm.
[0096] The material of the gasket is not particularly limited, and any known rubber material or resin material having insulating properties can be selected. Examples of rubber and resin materials that can be used include natural rubber (NR), styrene butadiene rubber (SBR), chloroprene rubber (CR), butadiene rubber (BR), acrylonitrile-butadiene rubber (NBR), silicone rubber (SR), ethylene-propylene rubber (EPT), ethylene-propylene-diene rubber (EPDM), fluororubber (FR), isobutylene-isoprene rubber (IIR), urethane rubber (UR), and chlorosulfonated polyethylene rubber (CSM). Fluororesin materials include polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkylvinylether copolymer (PFA), tetrafluoroethylene-ethylene copolymer (ETFE), and chlorotrifluoroethylene-ethylene copolymer (ECTFE). Resin materials include polyphenylene sulfide (PPS), polyethylene, polyimide, and polyacetal. Among these, ethylene-propylene-diene rubber (EPDM) and fluororubber (FR) are particularly suitable in terms of elastic modulus and alkali resistance.
[0097] (Header) The alkaline water electrolysis cell preferably has a cathode chamber and an anode chamber for each electrolysis cell. In order to continuously perform the electrolysis reaction in the electrolysis cell, it is necessary to continuously supply an electrolyte containing a sufficient amount of the raw materials to be consumed by electrolysis to the cathode chamber and the anode chamber of each electrolysis cell.
[0098] The electrolytic cells are connected to electrolyte supply and discharge pipes called headers that are common to multiple electrolytic cells. In general, the anode distribution pipe is called the anode inlet header, the cathode distribution pipe is called the cathode inlet header, the anode collection pipe is called the anode outlet header, and the cathode collection pipe is called the cathode outlet header. The elements are connected to each electrolyte distribution pipe and each electrolyte collection pipe via hoses, etc.
[0099] The material of the header is not particularly limited, but it is necessary to adopt a material that can sufficiently withstand the corrosiveness of the electrolyte used and the operating conditions such as pressure, temperature, etc. The header material may be iron, nickel, cobalt, PTFE, ETFE, PFA, polyvinyl chloride, polyethylene, etc.
[0100] The internal header type refers to a type in which the alkaline water electrolysis cell and the header (a tube for distributing or collecting the electrolyte) are integrated. As an example of the internal header type, an anode inlet header and a cathode inlet header are provided in a part of a lower portion of an outer frame at the end edge of the partition wall, and similarly, an anode outlet header and a cathode outlet header are provided in a part of an upper portion of an outer frame at the end edge of the partition wall. Note that the outer frame and the anode chamber or the cathode chamber are connected by an electrolyte inlet or electrolyte outlet through which the electrolyte passes.
[0101] The external header type refers to a type in which the alkaline water electrolysis cell and the header (the tube for distributing or collecting the electrolyte) are independent. In an external header type alkaline water electrolysis cell, an anode inlet header and a cathode inlet header are provided independently, running parallel to the electrolytic cell in a direction perpendicular to the current-carrying surface of the electrolytic cell. The anode inlet header and the cathode inlet header are connected to each element by hoses.
[0102] In addition, the internal header type and external header type electrolytic cells for alkaline water electrolysis may have therein a gas-liquid separation box for separating the gas generated by electrolysis from the electrolytic solution. The installation position of the gas-liquid separation box is not particularly limited, and the gas-liquid separation box may be installed between the anode chamber and the anode outlet header or between the cathode chamber and the cathode outlet header.
[0103] (electrolyte) In the alkaline water electrolysis cell of this embodiment, a cathode chamber frame having a cathode attached thereto and an anode chamber frame having an anode attached thereto are disposed via a partition wall. That is, the anode chamber and the cathode chamber are separated by the partition wall. An electrolytic solution is supplied to the anode chamber and the cathode chamber. The electrolyte may be one generally used for water electrolysis. For example, an aqueous solution of potassium hydroxide or an aqueous solution of sodium hydroxide may be used. The electrolyte concentration is preferably 1N or more and 12N or less, more preferably 6N or more and 10N or less.
[0104] In the alkaline water electrolysis cell of this embodiment, which includes the above-mentioned anode and cathode and in which an electrolytic solution is circulated, a current is applied to the alkaline water electrolysis cell to perform water electrolysis, thereby producing hydrogen at the cathode. In this case, for example, a variable power supply can be used as the power supply. A variable power supply is a power supply derived from a renewable energy power plant whose output fluctuates in units of a few seconds to a few minutes, unlike a power supply that provides a stable output, such as grid power. The method of generating renewable energy is not particularly limited, and examples thereof include solar power generation and wind power generation. For example, in the case of electrolysis using an alkaline water electrolysis cell, cationic electrolytes in the electrolytic solution move from the anode chamber of an element through a diaphragm to the cathode chamber of an adjacent element, and anionic electrolytes move from the cathode chamber of an element through a diaphragm to the anode chamber of an adjacent element. Thus, the current during electrolysis flows along the direction in which the elements are connected in series. That is, the current flows from the anode chamber of one element to the cathode chamber of the adjacent element through the diaphragm. As a result of electrolysis, oxygen gas is produced in the anode chamber and hydrogen gas is produced in the cathode chamber.
[0105] The bipolar electrolytic cell 65 of this embodiment can be used in the bipolar electrolytic cell 50, the electrolytic device 70 for alkaline water electrolysis, etc. An example of the electrolytic device 70 for alkaline water electrolysis includes an apparatus including the bipolar electrolytic cell 50 of this embodiment, a liquid delivery pump 71 for circulating the electrolytic solution, a gas-liquid separation tank 72 for separating the electrolytic solution from hydrogen and / or oxygen, and a water supply device for supplying water consumed by electrolysis. The alkaline water electrolysis apparatus 70 may further include a rectifier 74, an oxygen concentration meter 75, a hydrogen concentration meter 76, a flow meter 77, a pressure meter 78, a heat exchanger 79, a pressure control valve 80, and the like.
[0106] In the alkaline water electrolysis method using the alkaline water electrolysis apparatus, the current density applied to the electrolytic cell is 1 kA / m 2 ~20kA / m 2 Preferably, 6 kA / m 2 ~15kA / m 2 It is even more preferable that: In particular, when a variable power supply is used, it is preferable to set the upper limit of the current density within the above range.
[0107] In the bipolar electrolytic cell of this embodiment, the anode for alkaline water electrolysis is provided with a current of 6 kA / m 2 After passing an oxidation current of 15 A / m2 for 1 hour, a reduction current of 15 A / m2 is passed. The cumulative discharge amount until the potential reaches +0.12 V (vs. RHE) is 6 kA / m2 to the cathode for hydrogen generation. 2 After applying a reduction current of 15A / m for 1 hour 2 It is preferable that the amount of discharge is greater than the cumulative discharge amount required to pass an oxidation current of +1.12 V (vs. RHE) when the potential reaches +1.12 V. This makes the potential fluctuation due to reverse current smaller at the anode than at the cathode, suppressing deterioration of the anode due to reverse current and making it possible to maintain a lower cell voltage.
[0108] From the above viewpoint, the anode is provided with 6 kA / m 2 After passing an oxidation current of 15A / m for 1 hour, 2 The cumulative discharge amount until the potential reaches +0.12V (vs. RHE) is 10,000C / m 2 More than 300000C / m 2 It is preferable that:
[0109] <Hydrogen production method> The hydrogen production method of the present embodiment involves electrolyzing alkali-containing water in an electrolytic cell to produce hydrogen, and can be carried out using the alkaline water electrolysis cell of the present embodiment.
[0110] Details of the alkaline water electrolysis cell of this embodiment are as described above. In the hydrogen production method of the present embodiment, hydrogen can be produced by electrolyzing water containing alkali using a variable power supply that involves repeating positive current application and cessation of positive current application.
[0111] Although the cathode for hydrogen generation according to the embodiment of the present invention, the bipolar electrolytic cell according to the embodiment of the present invention, the alkaline water electrolysis cell according to the embodiment of the present invention, and the hydrogen production method according to the embodiment of the present invention have been illustrated and described with reference to the drawings, these are not limited to the above examples, and appropriate modifications can be made to the above embodiments. EXAMPLES
[0112] The present invention will be described below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples.
[0113] (Example 1-1) A bipolar element was produced according to the following steps, which was designated as Example 1-1.
[0114] -Cathode 1- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, a dinitrodiammine Pt nitric acid solution (Tanaka Kikinzoku, Pt concentration: 100 g / L), Y nitrate hexahydrate (Kanto Kagaku, 4N), and water were mixed so that the molar ratio of Pt element to Y element was 70:30 to prepare coating solution 1.
[0115] -Coating process- The conductive base material after heating and baking was immersed in a vat containing coating liquid 1 and then removed, and the coating liquid remaining in the mesh of the conductive base material was wiped off with an air blower (dip method).
[0116] -Precursor layer formation process- The conductive substrate subjected to the coating step was dried at 60° C. for 10 minutes to form a precursor layer.
[0117] - Firing process - The conductive substrate on which the precursor layer was formed was heated and baked in a muffle furnace at 500° C. for 10 minutes to pyrolyze the precursor layer. This cycle of the dip coating step, the precursor layer forming step, and the firing step was repeated 17 times, followed by post-firing at 500° C. for 1 hour in an air atmosphere to prepare a cathode 1. The weight of the cathode 1 was measured using an electronic balance, and the difference between the weight and the weight of the conductive substrate before the formation of the catalyst layer was divided by the area of 8.5 cm×17.0 cm to calculate the weight of the catalyst layer per unit area. The weight of the catalyst layer was calculated assuming that it was the total weight of PtO and Y2O3 contained in the catalyst layer.
[0118] -Anode 1- The anode 1 was made of Ni expand metal having a SW of 3.0 mm, a LW of 4.5 mm, a thickness of 0.75 mm, and an aperture ratio of 54%.
[0119] -Partition walls, outer frames- The bipolar element used had a partition wall separating the anode and cathode and an outer frame surrounding the partition wall. All of the materials of the members that come into contact with the electrolyte, such as the partition wall and the frame of the bipolar element, were made of nickel.
[0120] -Conductive elastic body- The conductive elastic body used was made by weaving nickel wire with a wire diameter of 0.15 mm and corrugating it to a wave height of 5 mm. It had a thickness of 5 mm, a repulsive force of 150 g / cm2 at 50% compression deformation, and a mesh size of about 5 meshes.
[0121] -diaphragm- 135 g of zirconium oxide (trade name "EP Zirconium Oxide", manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd.) and 210 g of N-methyl-2-pyrrolidone (manufactured by Wako Pure Chemical Industries, Ltd.) were charged into a ball mill pot with a capacity of 1000 mL containing 1 kg of SUS balls with a particle size of 0.5 mm. These were stirred at a rotation speed of 70 rpm in an atmosphere of 25°C for 3 hours to disperse and obtain a mixture. The obtained mixture was filtered through a stainless steel sieve (mesh size 30) to separate the balls from the mixture. 45 g of polysulfone ("Udel" (registered trademark), manufactured by Solvay Advanced Polymers, Inc.) and 18 g of polyvinylpyrrolidone (weight average molecular weight (Mw) 900000, manufactured by Wako Pure Chemical Industries, Ltd.) were added to the mixture from which the balls were separated, and the mixture was stirred and dissolved at 60°C for 12 hours using a three-one motor to obtain a coating liquid with the following component composition. Polysulfone: 15 parts by weight Polyvinylpyrrolidone: 6 parts by weight N-methyl-2-pyrrolidone: 70 parts by weight Zirconium oxide: 45 parts by weight The above coating liquid was applied to both surfaces of a substrate, a polyphenylene sulfide mesh (manufactured by Kureha Co., Ltd., film thickness 280 μm, mesh size 358 μm, fiber diameter 150 μm), using a comma coater so that the coating thickness was 150 μm on each side. Immediately after coating, the substrate coated with the coating liquid was exposed to steam from a coagulation bath containing a 30° C. pure water / isopropanol mixture (manufactured by Wako Pure Chemical Industries, Ltd., pure water / isopropanol = 50 / 50 (v / v)) for 2 minutes. Immediately thereafter, the substrate coated with the coating liquid was immersed in the coagulation bath for 4 minutes. Then, a coating film was formed on the substrate surface by coagulating the polysulfone. The coating film was then thoroughly washed with pure water to obtain a porous membrane. The average pore size of this porous membrane was 0.3 μm in terms of water permeability at 90°C. The thickness was 580 μm. The porosity was 43%. The mode diameter of ZrO2 was 5.0 μm. The ratio of the mode diameter of the inorganic particles to the average pore size of the porous membrane (mode diameter / average pore size) was 2.6.
[0122] -gasket- The gasket used was a square with a thickness of 4.0 mm, width of 18 mm, and inner dimensions of 504 mm square, with an opening on the inside that was the same dimensions as the electrode chamber in a plan view, and a slit structure for inserting and holding the diaphragm. The slit structure was designed with a 0.4 mm gap in the center of the thickness direction of the inner wall of the opening, for inserting and holding the diaphragm. This gasket was made of EPDM rubber, and had a tensile stress of 4.0 MPa at 100% deformation.
[0123] -Zero gap type multi-pole element- The external header type zero gap cell unit 60 is a rectangle of 540 mm x 620 mm, and the area of the current-carrying surface of the anode 2a and cathode 2c is 500 mm x 500 mm. The cathode side of the zero gap type bipolar element 60 has a cathode chamber 5c in which the cathode 2c, conductive elastomer 2e, and cathode current collector 2r are laminated and connected to the partition wall 1 via the cathode rib 6, and in which the electrolyte flows. The anode side has an anode chamber 5a in which the anode 2a is connected to the partition wall 1 via the anode rib 6, and in which the electrolyte flows (FIGS. 3 and 4). The depth of the anode chamber 5a (anode chamber depth, the distance between the partition wall and the anode in FIG. 4) was 25 mm, and the depth of the cathode chamber 5c (cathode chamber depth, the distance between the partition wall and the cathode current collector in FIG. 4) was 25 mm, and the material was nickel. The thickness of the nickel partition wall 1 to which the nickel anode rib 6 with a height of 25 mm and a thickness of 1.5 mm and the nickel cathode rib 6 with a height of 25 mm and a thickness of 1.5 mm were attached by welding was 2 mm. A nickel expand base material that had been blasted in advance was used as the cathode current collector 2r. The thickness of the base material was 1 mm, and the aperture ratio was 54%. The conductive elastic body 2e was fixed onto the cathode current collector 2r by spot welding. As shown in FIG. 5, a nozzle 9a leading to the cathode chamber was provided on the side of the element for the portion X enclosed by the dashed line in FIG. 4. The Pt wire 8 coated with PFA resin was inserted into an EPDM disk 9d and a PTFE disk 9c, which had holes in the center that matched the diameter of the PFA-coated Pt wire 8, and then inserted into the nozzle 9a, and the EPDM disk d and the PTFE disk 9c were fastened together with a cap nut 9b. In this way, the PFA-coated Pt wire can be introduced into the cell without the electrolyte leaking to the outside. The PFA-coated Pt wire 8 had about 10 mm of its PFA coating peeled off from one end of the element outside, so that the Pt wire 8 could be held with an alligator clip. Furthermore, for the portion Y enclosed by the two-dot dashed line in Figure 4, as shown in Figure 6, the tip of the PFA-coated Pt wire a introduced into the cathode chamber of the element had the PFA coating peeled off by about 0.5 mm so that the Pt wire would come into contact with the hydrogen bubbles generated by electrolysis. This PFA-coated Pt wire a was bent in the cathode chamber and fixed near the surface opposite the diaphragm of the cathode 2c(2) through the through hole of the current collector 2r and the gap between the conductive elastic body 2e so that the tip of the Pt wire would not come into contact with the cathode 2c(2), the conductive elastic body 2e, or the current collector 2r (Figure 6). In this way, the Pt wire comes into contact with the hydrogen bubbles generated by electrolysis, forming an RHE reference electrode where the potential of the Pt wire is at the hydrogen generation potential. By stacking these zero-gap type bipolar elements via a gasket that holds the diaphragm, a zero-gap structure Z in which the anode 2a and the cathode 2c are pressed against the diaphragm 4 can be formed.
[0124] (Example 1-2) A bipolar element was prepared as Example 1-2 under the same conditions as in Example 1-1, except that a cathode 2 prepared as described below was used. -Cathode 2- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, a dinitrodiammine Pt nitric acid solution (Tanaka Kikinzoku, Pt concentration: 100 g / L), Y nitrate hexahydrate (Kanto Kagaku, 4N), and water were mixed so that the molar ratio of Pt element to Y element was 80:20 to prepare coating solution 2. A cathode 2 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 15 times using this coating liquid 2, and the weights of the catalyst and Pt were calculated.
[0125] (Examples 1-3) A bipolar element was prepared as Example 1-3 under the same conditions as in Example 1-1, except that a cathode 3 prepared as described below was used. -Cathode 3- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, a dinitrodiammine Pt nitric acid solution (Tanaka Kikinzoku, Pt concentration: 100 g / L), Y nitrate hexahydrate (Kanto Kagaku, 4N), and water were mixed so that the molar ratio of Pt element to Y element was 90:10, to prepare coating solution 3. A cathode 3 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 13 times using this coating liquid 3, and the weights of the catalyst and Pt were calculated.
[0126] (Examples 1 to 4) A bipolar element was produced under the same conditions as in Example 1-1, except that a cathode 4 produced as described below was used, and this was designated Example 1-4. -Cathode 4- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, dinitrodiammine Pt nitric acid solution (Tanaka Precious Metals, Pt concentration: 100 g / L), Ni(II) nitrate hexahydrate (Kanto Chemical, 3N5), and water were mixed so that the molar ratio of Pt element to Ni element was 75:25 to prepare coating solution 4. A cycle of the coating step and the precursor layer forming step was repeated five times to form a first layer of the catalyst layer on the conductive substrate using this coating solution 4. The weight of this layer was measured using an electronic balance, and the difference from the weight of the conductive substrate before the formation of the first layer was divided by the area of 8.5 cm × 17.0 cm to calculate the weight of the first layer per unit area. The weight of the first layer was then calculated assuming that the weight of the first layer was the total weight of Pt and NiO contained in the first layer. Next, a dinitrodiammine Pt nitric acid solution (Tanaka Kikinzoku, Pt concentration: 100 g / L), Y nitrate hexahydrate (Kanto Kagaku, 4N), and water were mixed so that the molar ratio of Pt element to Y element was 75:25 to prepare coating solution 5. The cycle of the coating step and the precursor layer forming step was repeated 11 times using this coating solution 5 to form a second catalyst layer on the conductive substrate on which the first layer had been formed, and then post-baking was carried out in an air atmosphere at 500° C. for 1 hour to prepare a cathode 4. The weight of the cathode 4 was measured using an electronic balance, and the difference between the weight and the weight of the conductive base material before the formation of the second layer was divided by the area of 8.5 cm×17.0 cm to calculate the weight of the second layer per unit area. The weight of the second layer was calculated assuming that the weight of the second layer was the total weight of Pt and Y2O3 contained in the catalyst layer. The weight of the catalyst layer was calculated from the sum of the weights of the first layer and the second layer, and the weight of Pt contained in the catalyst layer was calculated from the sum of the weight of Pt contained in the first layer and the weight of Pt contained in the second layer.
[0127] (Examples 1 to 5) A bipolar element was produced under the same conditions as in Example 1-1, except that a cathode 5 produced as described below was used, and this was designated Example 1-5. -Cathode 5- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, dinitrodiammine Pt nitric acid solution (Tanaka Precious Metals, Pt concentration: 100 g / L), yttrium nitrate hexahydrate (Kanto Chemical, 4N), Ni(II) nitrate hexahydrate (Kanto Chemical, 3N5), and water were mixed so that the molar ratio of Pt element, Y element, and Ni element was 75:17:8, to prepare coating solution 6. A cathode 5 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the baking step was repeated 17 times using this coating liquid 6. The weight was measured using an electronic balance, and the difference from the weight of the conductive base material before the catalyst layer was formed was divided by the area of 8.5 cm × 17.0 cm to calculate the weight of the catalyst layer per unit area. The weight of the catalyst layer was then calculated assuming that it was the total weight of PtO, Y2O3, and NiO contained in the catalyst layer.
[0128] (Examples 1 to 6) A bipolar element was produced under the same conditions as in Example 1-1, except that a cathode 6 produced as described below was used, and this was designated Example 1-6. -Cathode 6- An electrolytic Ni foil with a gauge thickness of 16 μm was used as the conductive substrate. One side of this Ni foil was roughened by electrolytic Ni plating. The arithmetic mean roughness Ra of the roughened surface was 0.9 μm. This Ni foil was perforated by punching. The aperture ratio was 49%. This conductive substrate was cut into a size of 8.5 cm x 17.0 cm, ultrasonically cleaned in isopropyl alcohol at room temperature for 10 minutes, and then dried. The conductive substrate after drying was heated and sintered at 400° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. In the coating step, Coating Liquid 5 was used. Coating Liquid 5 was sprayed onto the roughened side of the conductive substrate using a sprayer with 0.1 MPa compressed air as a carrier gas, and then the conductive substrate was dried at 60° C. for 10 minutes to form a precursor layer. The conductive substrate on which the precursor layer was formed was heated and baked at 400° C. for 10 minutes in a muffle furnace to pyrolyze the precursor layer. This cycle of the spray coating step, the precursor layer forming step, and the firing step was repeated 17 times, followed by post-firing at 400° C. for 1 hour in an air atmosphere to produce a cathode 6. The weight of this cathode 6 was measured using an electronic balance, and the difference between this weight and the weight of the conductive substrate before the formation of the catalyst layer was divided by the area of 8.5 cm×17.0 cm to calculate the weight of the catalyst layer per unit area. The weight of the catalyst layer was calculated assuming that it was the total weight of PtO and Y2O3 contained in the catalyst layer.
[0129] (Examples 1 to 7) A bipolar element was produced under the same conditions as in Example 1, except that a cathode 7 produced as described below was used, and this was designated Example 1-7. -Cathode 7- A cathode 7 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 10 times using the coating liquid 1, and the weights of the catalyst and Pt were calculated.
[0130] (Examples 1 to 8) A bipolar element was prepared under the same conditions as in Example 1-1, except that a cathode 8 prepared as described below was used, and this was designated Example 1-8. -Cathode 8- A cathode 8 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 40 times using the coating liquid 1, and the weights of the catalyst and Pt were calculated.
[0131] (Examples 1 to 9) A bipolar element was produced under the same conditions as in Example 1-1, except that a cathode 9 produced as described below was used, and this was designated Example 1-9. -Cathode 9- A cathode 9 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated six times using the coating liquid 1, and the weights of the catalyst and Pt were calculated.
[0132] (Examples 1 to 10) A bipolar element was produced under the same conditions as in Example 1-1, except that a cathode 10 produced as described below was used, and this was designated Example 1-10. -Cathode 10- A cathode 10 was produced under the same conditions as in Example 1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 48 times using Coating Liquid 1, and the weights of the catalyst and Pt were calculated.
[0133] (Examples 1 to 11) A plain weave mesh made of 40-mesh woven nickel fine wires with a diameter of 0.15 mm was used as the anode 2. Using this anode 2, a zero-gap type bipolar element using the same conductive elastic body, current collector, and ribs as the cathode side was used on the anode side. Except for this, a bipolar element was produced under the same conditions as in Example 1-1, and designated Example 1-11.
[0134] (Examples 1-12) Example 1-12 was prepared by producing a bipolar element under the same conditions as in Example 1-1, except that an anode 3 made of Ni expand metal with a SW of 3.0 mm, a LW of 4.5 mm, a thickness of 0.75 mm, and an aperture ratio of 54% that had been subjected to blasting treatment was used.
[0135] (Comparative Example 1-1) A bipolar element was prepared as Comparative Example 1-1 under the same conditions as in Example 1-1, except that a cathode 101 prepared as described below was used. -Cathode 101- A dinitrodiammine Pt nitric acid solution (Tanaka Precious Metals, Pt concentration: 100 g / L) and water were mixed to prepare coating solution 7. A cathode 101 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the baking step was repeated 12 times using this coating liquid 7. The weight of the catalyst layer was then calculated assuming that the weight of the PtO contained in the catalyst layer was the weight of the Pt contained in the catalyst layer.
[0136] (Comparative Example 1-2) A bipolar element was prepared as Comparative Example 1-2 under the same conditions as in Comparative Example 1-1, except that a cathode 102 prepared as described below was used. -Cathode 102- A cathode 102 was produced under the same conditions as in Comparative Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 20 times using the coating solution 7. The weight of the catalyst layer and the weight of Pt contained in the catalyst layer were calculated in the same manner as in Comparative Example 1-1.
[0137] (Comparative Example 1-3) A bipolar element was prepared as Comparative Example 1-3 under the same conditions as in Example 1-1, except that a cathode 103 prepared as described below was used. -Cathode 103- Coating solution 8 was prepared by mixing dinitrodiammine Pt nitric acid solution (Tanaka Precious Metals, Pt concentration: 100 g / L), Ce(III) nitrate hexahydrate (Kanto Chemical, Kaga special grade), and water so that the molar ratio of Pt element to Ce element was 50:50. A cathode 103 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the baking step was repeated 13 times using this coating liquid 8. The weight of the catalyst layer was then calculated assuming that the weight of the catalyst layer was the total weight of PtO and CeO2 contained in the catalyst layer.
[0138] (Comparative Examples 1-4) A bipolar element was prepared as Comparative Example 1-4 under the same conditions as in Example 1-1, except that a cathode 104 prepared as described below was used. -Cathode 104- A cathode 104 was produced in the same manner as in Example 1, except that the cycle of the coating step, the precursor layer forming step, and the baking step was repeated eight times using Coating Liquid 8. The weight of the catalyst layer was then calculated assuming that the weight of the catalyst layer was the total weight of Pt and CeO2 contained in the catalyst layer.
[0139] (Comparative Examples 1-5) A bipolar element was prepared as Comparative Example 1-5 under the same conditions as in Example 1-1, except that a cathode 105 prepared as described below was used. -Cathode 105- Coating solution 9 was prepared by mixing dinitrodiammine Pt nitric acid solution (Tanaka Kikinzoku, Pt concentration: 100 g / L), Ce(III) nitrate hexahydrate (Kanto Kagaku, Kaga special grade), and water so that the molar ratio of Pt element to Ce element was 64:36. A cathode 105 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the baking step was repeated 15 times using this coating liquid 9. The weight of the catalyst layer was then calculated assuming that the weight of the catalyst layer was the total weight of PtO and CeO2 contained in the catalyst layer.
[0140] The following tests (1) to (4) were carried out for each of the Examples and Comparative Examples. The results are shown in Table 1. Test (1) Measurement method for the amount of discharge of the cathode The discharge amount of the cathode was calculated by the three-electrode method as follows: The measurement device used was a potentiogalvanostat PARSTAT MC 1000 manufactured by Princeton Applied Research. The same cathode as that used in each Example and Comparative Example was cut to 18 mm x 17 mm and fixed to a PTFE-coated nickel rod with a nickel screw. A Pt mesh was used as the counter electrode, and a silver-silver chloride (Ag / AgCl) glass electrode was used as the reference electrode. A 34 wt% aqueous potassium hydroxide solution was used as the electrolyte. The temperature of this electrolyte was adjusted to 70°C. First, a current density of -6 kA / m 2 After applying a reduction current of +15A / m for 1 hour, immediately after the open circuit voltage measurement, 2 An oxidation current of +15 A / m was applied. At this time, the potential of the cathode gradually increased from the hydrogen generation potential to a more noble potential. When the potential of the cathode reached +1.12 V (vs. RHE), the current was stopped. 2 The time from when the current started to when it stopped flowing and the absolute value of the current density of 15A / m 2 The discharge rate of the cathode is calculated by multiplying it by the current (unit: C / m 2 ) was calculated.
[0141] Test (2) Method for measuring the electric double layer capacitance of the cathode The electric double layer capacitance of the cathode was determined by the three-electrode method as follows. The measurement device used was a potentiogalvanostat PARSTAT MC 1000 manufactured by Princeton Applied Research. The same cathode as that used in each Example and Comparative Example was cut to 18 mm x 17 mm and fixed to a PTFE-coated nickel rod with a nickel screw. A Pt mesh was used as the counter electrode, and a silver-silver chloride (Ag / AgCl) glass electrode was used as the reference electrode. A 34 wt% aqueous potassium hydroxide solution was used as the electrolyte. The temperature of this electrolyte was adjusted to 70°C. First, a current density of -6 kA / m 2 A reduction current of 0.47 V (vs. RHE) was applied for 1 hour. Then, cyclic voltammetry was performed with a potential sweep width of 0.40 V to 0.54 V (vs. RHE) at sweep rates of 50, 100, 200, and 400 mV / sec for 5 cycles each. Then, in the 5th cycle at each sweep rate, the average value of the oxidation current and reduction current when the cathode potential was 0.47 V (vs. RHE) was plotted on the vertical axis and the sweep rate on the horizontal axis, and the electric double layer capacity (unit: C / cm) was calculated from the slope of the plot. 2 ) was calculated.
[0142] Test (3) Method for measuring the discharge amount of the anode The discharge amount of the anode was calculated by the three-electrode method as follows: The measurement device used was a potentiogalvanostat PARSTAT MC 1000 manufactured by Princeton Applied Research. The same anode used in each Example and Comparative Example was cut to 18 mm x 17 mm and fixed to a PTFE-coated nickel rod with a nickel screw. A Pt mesh was used as the counter electrode, and a silver-silver chloride (Ag / AgCl) glass electrode was used as the reference electrode. A 34 wt% aqueous potassium hydroxide solution was used as the electrolyte. The temperature of this electrolyte was adjusted to 70°C. First, the current density was +6 kA / m 2 After passing an oxidation current of -15A / m for 1 hour, the open circuit voltage was immediately measured without any intervening measurements. 2 A reduction current of -15 A / m was applied. At this time, the anode potential gradually decreased from the oxygen evolution potential to a less noble potential. When the anode potential reached +0.12 V (vs. RHE), the current was stopped. 2 The time from when the current started to when it stopped flowing and the absolute value of the current density of 15A / m 2The discharge rate of the anode is calculated by multiplying the 2 ) was calculated.
[0143] Test (4) Bipolar electrolytic cell power-off cycle test 1 For each of the Examples and Comparative Examples, a bipolar electrolytic cell was prepared as follows, stacked in the order shown in Fig. 4. A bipolar electrolytic cell was constructed by stacking an anode terminal cell unit 51a using the anode described in each Example and Comparative Example, the diaphragm described above, a portion in which three sets of zero gap type bipolar elements of each Example and Comparative Example were stacked with the diaphragm sandwiched therebetween, the diaphragm described above, and a cathode terminal cell 51c using the cathode described in each Example and Comparative Example, in that order. Using this bipolar electrolytic cell, the electrolysis device shown in FIG. 3 was fabricated. The electrolysis device includes a bipolar electrolytic cell 50, a liquid feed pump 71 for circulating the electrolyte, and a gas-liquid separation tank 72 for separating the electrolyte from hydrogen and / or oxygen. The gas-liquid separation tank 72 and the bipolar electrolytic cell 50 are filled with an electrolyte that is a 30% KOH aqueous solution. The liquid feed pump 71 circulates the electrolyte through the anode chamber 5a of the bipolar electrolytic cell 50, the gas-liquid separation tank 72 for the anode, and the anode chamber 5a, and also through the cathode chamber 5c of the bipolar electrolytic cell 50, the gas-liquid separation tank 72 for the cathode, and the cathode chamber 5c. The temperature was adjusted to 90°C. In the electrolysis device, the gas separated in the gas-liquid separation tank 72 is recovered through a pressure gauge 78, a pressure control valve 80, and an oxygen concentration meter 75 or a hydrogen concentration meter 76. Furthermore, the power can be controlled by a rectifier 74. Furthermore, a flow meter 77 and a heat exchanger 79 are provided in the flow path of the circulating electrolyte. Furthermore, the arrows in Fig. 3 indicate the flow directions of the circulating liquid (electrolyte) and the gas. The electrolyte contact part of the circulation flow path was made of SGP carbon steel piping with Teflon (registered trademark) lining, and 20A piping was used. The gas-liquid separation tank 72 had a height of 1400 mm and a volume of 1 m 3 The following was used. The gas-liquid separation tank 72 has a height of 1400 mm and a volume of 1 m 3 The following items were used. The liquid volume in each gas-liquid separation tank 72 was set to about 50% of the design volume. In the external header type electrolytic cell, four external pipes (anode inlet header 10ai, cathode inlet header 10ci, anode outlet header 10ao, cathode outlet header 10co) for the electrolyte to flow are provided in the electrolysis frame that serves as the housing of the bipolar element. Each of these external pipes is connected to each electrode chamber of the electrolytic cell by an external hose. This piping structure is called the external header structure. The external header piping is divided into a cathode side external header piping and an anode side external header piping. Therefore, in each element, the electrolyte enters the cathode chamber 5c from the cathode inlet header 10ci through the external hose, and flows from the cathode chamber 5c to the cathode outlet header 10co through the external hose. Similarly, on the anode side, the electrolyte enters the anode chamber 5a from the anode inlet header 10ai through the external hose, and flows from the anode chamber 5a to the anode outlet header 10ao through the external hose. Since the inlet header of the external header is on the lower side of the electrolysis frame and the outlet header is on the upper side of the electrolysis frame, the electrolyte flows from the bottom to the top. It also rises in a direction approximately perpendicular to the electrode surface. A thermocouple is installed in the external hose of each cell, and the temperature difference before and after passing through the element can be measured. In this example, there are 29 anode chambers 5a and 29 cathode chambers 5c, and the structure is such that the electrolyte flows from the inlet header to the outlet header in each of the 29 chambers. In the cathode chamber 5c, hydrogen gas is generated by electrolysis, and in the anode chamber 5a, oxygen gas is generated, so that in the cathode outlet header 10co, a mixed phase flow of electrolyte and hydrogen gas is formed, and in the anode outlet header 10ao, a mixed phase flow of electrolyte and oxygen gas is formed. A current was applied from the rectifier 74 to the bipolar electrolytic cell 50 with respect to the areas of the cathode and anode under the conditions of Electrolysis Test 1 or Electrolysis Test 2 described below. The pressure inside the cell after the start of current application was measured with a pressure gauge 78, and the cathode side pressure was adjusted to 50 kPa and the oxygen side pressure to 49 kPa. The pressure was adjusted by a control valve 80 installed downstream of the pressure gauge 78. In the electrolysis device, the gas separated in the gas-liquid separation tank 72 is recovered through a pressure gauge 78, a pressure control valve 80, and an oxygen concentration meter 75 or a hydrogen concentration meter 76. Furthermore, the power can be controlled by a rectifier 74. Furthermore, a flow meter 77 and a heat exchanger 79 are provided in the flow path of the circulating electrolyte. The electrolysis apparatus for alkaline water electrolysis was produced using a rectifier, an oxygen concentration meter, a hydrogen concentration meter, a pressure gauge, a liquid delivery pump, a gas-liquid separation tank, a water supply unit, and the like that are all commonly used in the relevant technical fields.
[0144] When hydrogen generating electrolysis was performed using the above electrolysis apparatus, the potential of the zero gap type bipolar element was equal to the potential of the cathode, and the PTFE-coated Pt wire fixed near the cathode in the cathode chamber of the zero gap type bipolar element became an RHE electrode by contacting hydrogen generated by electrolysis and was at a hydrogen generating potential; therefore, the potential difference between the zero gap type bipolar element and the PTFE-coated Pt wire was measured, and this potential difference was taken as the cathode overvoltage. Using the above electrolysis device, the current density was 6 kA / m 2 Water electrolysis was performed continuously for 100 hours with positive current so that the electrolysis was stopped for 5 minutes. Then, the current was applied again at 6 kA / m 2 The positive current was applied for 5 minutes and then stopped for 5 minutes. Each of these 5 minutes of positive current application and 5 minutes of stoppage was counted as one current application / stop cycle, and 1500 current application / stop cycles were performed. The average value of the cell voltages of the two cells not including the anode terminal cell unit 51a and the cathode terminal cell 51c during the first 5 minutes of positive current application after 100 hours of positive current application was defined as the initial cell voltage, the average value of the cathode overvoltages of the two cells at this time was defined as the initial overvoltage, and the average value of the cathode overvoltages of the two cells during the positive current application included in the 1500th current application / stop cycle was defined as the post-test overvoltage. [Table 1]
[0145] In the test (4), in each of Comparative Examples 1-1 to 1-5, the cathode overvoltage increased by 60 mV or more after the test, whereas in each of Examples 1-1 to 1-12, the increase in overvoltage was suppressed to 30 mV or less, and it was found that the batteries exhibited significantly higher durability against 1,500 power interruptions. Furthermore, it was found that, although Examples 1-7 and 1-9 had smaller catalyst weights and Pt weights than Comparative Example 1-1, they showed higher durability than Comparative Example 1-1, and, although Examples 1-1 to 1-7, 1-9, 1-11, and 1-12 had smaller catalyst weights and Pt weights than Comparative Example 1-2, they showed higher durability than Comparative Example 1-2. These results demonstrate that a cathode having a catalyst layer containing Pt element and element R, which is electrochemically stable as a trivalent ion within the potential window of water from pH 7 to pH 16 inclusive, in the molar ratio specified by the present invention, has high durability.
[0146] In addition, the overvoltage of Example 1-1 increased by 6 mV after the test, whereas the overvoltage of Example 1-7 increased by 12 mV after the test, and the overvoltage of Example 1-9 increased by 26 mV after the test. It is believed that if the discharge amount is too small, the potential of the cathode becomes too noble when the current flow is stopped, causing more severe deterioration. It is also believed that if the catalyst layer weight is too low, durability decreases. From these results, it is believed that the discharge amount is 1500 C / m 2 The weight of the catalyst layer is preferably 4.5 g / m or more. 2 or more is preferable, and the Pt weight is 3.5 g / m 2 The above was found to be preferable. Furthermore, Example 1-8 had an initial overvoltage of 115 mV and an overvoltage after the test of 121 mV, whereas Example 1-10 had an initial overvoltage of 121 mV and an overvoltage after the test of 131 mV. Although both had high durability, they maintained a high overvoltage compared to other Examples. Since the oxide or hydroxide of element R contained in the catalyst layer is an insulator or a conductor with a higher electrical resistance than metals, it is believed that if the catalyst weight is too high, the electrical resistance will become high. From this result, the weight of the catalyst layer is 20 g / m 2 In the following, the weight of Pt is 15g / m 2 The following have been found to be preferred:
[0147] Furthermore, there is a positive correlation between the discharge amount of the cathode and the electric double layer capacity, and the electric double layer capacity is 0.01 F / cm 2 ~0.15F / cm 2 was found to be preferred.
[0148] Next, Examples 2-1 to 2-18 and Comparative Examples 2-1 to 2-6 will be described.
[0149] (Example 2-1) As in Example 1-1, a cathode 1 and an anode 1 were used.
[0150] (Example 2-2) As in Example 1-2, a cathode 2 and an anode 1 were used.
[0151] (Example 2-3) As in Example 1-3, a cathode 3 and an anode 1 were used.
[0152] (Examples 2-4) As in Example 1-4, a cathode 4 and an anode 1 were used.
[0153] (Examples 2-5) As in Example 1-5, a cathode 5 and an anode 1 were used.
[0154] (Examples 2-6) As in Example 1-6, a cathode 6 and an anode 1 were used.
[0155] (Examples 2-7) As in Example 1-7, a cathode 7 and an anode 1 were used.
[0156] (Examples 2-8) As in Example 1-8, a cathode 8 and an anode 1 were used.
[0157] (Examples 2-9) As in Example 1-9, a cathode 9 and an anode 1 were used.
[0158] (Examples 2-10) As in Example 1-10, a cathode 10 and an anode 1 were used.
[0159] (Example 2-11) As in Example 1-11, a cathode 1 and an anode 2 were used.
[0160] (Example 2-12) As in Example 1-12, a cathode 1 and an anode 3 were used.
[0161] (Example 2-13) The cathode 11 and the anode 1 prepared as follows were used. -Cathode 11- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, a dinitrodiammine Pt nitric acid solution (Tanaka Kikinzoku, Pt concentration: 100 g / L), Y nitrate hexahydrate (Kanto Kagaku, 4N), and water were mixed so that the molar ratio of Pt element to Y element was 65:35 to prepare coating solution 10. A cathode 11 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 15 times using this coating liquid 10, and the weights of the catalyst and Pt were calculated.
[0162] (Examples 2-14) The cathode 12 and the anode 1 prepared as follows were used. -Cathode 12- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, a dinitrodiammine Pt nitric acid solution (Tanaka Kikinzoku, Pt concentration: 100 g / L), Y nitrate hexahydrate (Kanto Kagaku, 4N), and water were mixed so that the molar ratio of Pt element to Y element was 95:5 to prepare coating solution 11. A cathode 12 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 17 times using this coating liquid 11, and the weights of the catalyst and Pt were calculated.
[0163] (Example 2-15) The cathode 13 and the anode 1 prepared as follows were used. -Cathode 13- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, a dinitrodiammine Pt nitric acid solution (Tanaka Precious Metals, Pt concentration: 100 g / L), Sc nitrate hydrate (Sigma-Aldrich, 99.9%), and water were mixed so that the molar ratio of Pt element to Sc element was 75:25, to prepare coating solution 11. A cathode 13 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 14 times using this coating liquid 11. The weight of the catalyst layer was then calculated assuming that the weight of the catalyst layer was the total weight of PtO and Sc2O3 contained in the catalyst layer.
[0164] (Example 2-16) The cathode 14 and the anode 1 prepared as follows were used. -Cathode 14- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, a cycle of the coating step and the precursor layer forming step was repeated four times using the coating liquid 3 to form a first layer of the catalyst layer on the conductive substrate. The weight was measured using an electronic balance, and the difference from the weight of the conductive substrate before the formation of the first layer was divided by the area of 8.5 cm × 17.0 cm to calculate the weight of the first layer per unit area. The weight of the first layer was calculated assuming that the weight of the first layer was the total weight of Pt and Y2O3 contained in the first layer. Next, a cycle of the coating step and the precursor layer forming step was repeated 10 times using the coating liquid 1 to form a second layer of the catalyst layer on the conductive substrate on which the first layer had been formed. Further, post-baking was performed in an air atmosphere at 500° C. for 1 hour to prepare a cathode 14. The weight of the cathode 17 was measured using an electronic balance, and the difference between the weight and the weight of the conductive substrate before the formation of the second layer was divided by the area of 8.5 cm×17.0 cm to calculate the weight of the second layer per unit area. The weight of the second layer was calculated assuming that the weight of the second layer was the total weight of Pt and Y2O3 contained in the catalyst layer. The weight of the catalyst layer was calculated from the sum of the weights of the first layer and the second layer, and the weight of Pt contained in the catalyst layer was calculated from the sum of the weight of Pt contained in the first layer and the weight of Pt contained in the second layer.
[0165] (Example 2-17) The cathode 15 and the anode 1 prepared as follows were used. -Cathode 15- An electrolytic Ni foil with a gauge thickness of 16 μm was used as the conductive substrate. One side of this Ni foil was roughened by electrolytic Ni plating. The arithmetic mean roughness Ra of the roughened surface was 0.6 μm. This Ni foil was perforated by punching. The aperture ratio was 49%. This conductive substrate was cut into a size of 8.5 cm x 17.0 cm, ultrasonically cleaned in isopropyl alcohol at room temperature for 10 minutes, and then dried. The conductive substrate after drying was heated and sintered at 400° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. In the coating step, Coating Liquid 5 was used. Coating Liquid 5 was sprayed onto the roughened side of the conductive substrate using a sprayer with 0.1 MPa compressed air as a carrier gas, and then the conductive substrate was dried at 60° C. for 10 minutes to form a precursor layer. The conductive substrate on which the precursor layer was formed was heated and baked at 400° C. for 10 minutes in a muffle furnace to pyrolyze the precursor layer. This cycle of the spray coating step, the precursor layer forming step, and the firing step was repeated 15 times, followed by post-firing at 400° C. for 1 hour in an air atmosphere to produce a cathode 15. The weight of this cathode 15 was measured using an electronic balance, and the difference between this weight and the weight of the conductive substrate before the formation of the catalyst layer was divided by the area of 8.5 cm×17.0 cm to calculate the weight of the catalyst layer per unit area. The weight of the catalyst layer was calculated assuming that it was the total weight of PtO and Y2O3 contained in the catalyst layer.
[0166] (Example 2-18) The cathode 16 and the anode 1 prepared as follows were used. -Cathode 16- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, dinitrodiammine Pt nitrate solution (Tanaka Precious Metals, Pt concentration: 100 g / L), yttrium nitrate hexahydrate (Kanto Chemical, 4N), Pd nitrate solution (Tanaka Precious Metals, Pd concentration: 100 g / L), and water were mixed so that the molar ratio of Pt element, Y element, and Ni element was 75:17:8, to prepare coating solution 6. A cathode 5 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the baking step was repeated 15 times using this coating liquid 6. The weight was measured using an electronic balance, and the difference from the weight of the conductive base material before the catalyst layer was formed was divided by the area of 8.5 cm × 17.0 cm to calculate the weight of the catalyst layer per unit area. The weight of the catalyst layer was calculated assuming that it was the total weight of PtO, Y2O3, and PdO contained in the catalyst layer.
[0167] (Comparative Example 2-1) As in Comparative Example 1-1, a cathode 101 and an anode 1 were used.
[0168] (Comparative Example 2-2) As in Comparative Example 1-2, a cathode 102 and an anode 1 were used.
[0169] (Comparative Example 2-3) As in Comparative Example 1-3, a cathode 103 and an anode 1 were used.
[0170] (Comparative Example 2-4) As in Comparative Example 1-4, the cathode 104 and the anode 1 were used.
[0171] (Comparative Example 2-5) As in Comparative Example 1-5, a cathode 105 and an anode 1 were used.
[0172] (Comparative Example 2-6) The cathode 106 prepared as follows was used. -Cathode 106- The conductive substrate was a plain-woven mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at a mesh size of 40. The conductive substrate was blasted with alumina powder with a weight-average particle size of 100 μm or less and cut into a size of 8.5 cm × 17.0 cm. The substrate was then acid-treated in 6N hydrochloric acid at room temperature for 10 minutes, washed with water, and dried. The conductive substrate after drying was heated and sintered at 500° C. for 10 minutes in a muffle furnace to form a nickel oxide layer on the surface of the conductive substrate. The weight of the conductive substrate after heating and sintering was measured using a PG503-S electronic balance manufactured by Mettler Toledo K.K. Next, a dinitrodiammine Pt nitric acid solution (Tanaka Kikinzoku, Pt concentration: 100 g / L), Y nitrate hexahydrate (Kanto Kagaku, 4N), and water were mixed so that the molar ratio of Pt element to Y element was 45:55, to prepare coating solution 15. A cathode 106 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 26 times using this coating liquid 15, and the weights of the catalyst and Pt were calculated.
[0173] The above-mentioned tests (1) to (3) and the following test (5) were carried out for each of the examples and comparative examples. The results are shown in Table 2.
[0174] Test (5) Reverse current cycle test 1 simulating a 200-pair bipolar electrolytic cell A reverse current cycle test was carried out simulating a 200-pair bipolar electrolytic cell using a three-electrode method with a potentiogalvanostat PARSTAT MC 1000 manufactured by Princeton Applied Research, as follows. First, in a 200-pair bipolar electrolytic cell, the average value of the reverse current flowing through each cell after electrolysis was stopped was calculated to be 15 A / m2 using an equivalent circuit. Next, discharge curves were obtained at the above current densities for the cathode and anode described in each of the examples and comparative examples. The cathode was cut to 18mm x 17mm and fixed to a PTFE-coated nickel rod with a nickel screw. A Pt mesh was used as the counter electrode, and a silver-silver chloride (Ag / AgCl) glass electrode was used as the reference electrode. The electrolyte was a 34 wt% aqueous potassium hydroxide solution. The temperature of this electrolyte was adjusted to 70°C. First, a reduction current with a current density of -6kA / m2 was applied for 1 hour, and then an oxidation current with a current density of +15A / m2 was immediately applied without any open circuit voltage measurement. At this time, the potential of the cathode gradually increased from the hydrogen generation potential to a more noble potential. When the potential of the cathode reached +1.12V (vs RHE), the current was stopped. The absolute value of the integrated current charge obtained from the product of the current density and the current application time was plotted on the horizontal axis, and the cathode potential on the vertical axis to obtain the cathode discharge curve. Next, the anode was cut to 18mm x 17mm and fixed to a PTFE-coated nickel rod with a nickel screw. A Pt mesh was used as the counter electrode, and a silver-silver chloride (Ag / AgCl) glass electrode was used as the reference electrode. The electrolyte was a 34 wt% potassium hydroxide aqueous solution. The temperature of this electrolyte was adjusted to 70°C. First, an oxidizing current with a current density of +6kA / m2 was applied for 1 hour, and then a reducing current with a current density of -15A / m2 was immediately applied without any open circuit voltage measurement. At this time, the potential of the anode gradually decreased from the oxygen generation potential to a more noble potential. When the potential of the anode reached +0.12V (vs RHE), the current was stopped. The absolute value of the integrated current charge obtained from the product of the current density and the current application time was plotted on the horizontal axis, and the potential of the anode was plotted on the vertical axis to obtain the discharge curve of the anode. The discharge curve of the cathode and the discharge curve of the anode were then superimposed, and the potential at which they intersected was set as the potential that the reverse current would reach when the current was stopped. An example is shown in Figure 7. Using the reverse current density obtained as above and the ultimate potential of the reverse current in each of the examples and comparative examples as conditions, a reverse current cycle test was carried out as follows. The cathode was cut to 18 mm x 17 mm and fixed to a PTFE-coated nickel rod with a nickel screw. A Pt mesh was used as the counter electrode, and a silver-silver chloride (Ag / AgCl) glass electrode was used as the reference electrode. The electrolyte was a 34 wt% aqueous potassium hydroxide solution. The temperature of this electrolyte was adjusted to 70°C. In this state, the overvoltage at a current density of -6kA / m2 was measured. At this time, the ohmic loss that could not be completely eliminated even by using the three-electrode method was measured by the AC impedance method, and the overvoltage was corrected based on the measured value of the ohmic loss. Next, as a pretreatment of the cathode, a reduction current with a current density of -6kA / m2 was applied for 5 hours, and then an oxidation current of +15A / m2 was applied immediately without any open circuit voltage measurement. At this time, the potential of the cathode gradually increases from the hydrogen generation potential to a noble potential. When the potential of the cathode reached the reverse current reach potential of each example, a reduction current of -6kA / m2 was applied for 1 minute immediately without any open circuit voltage measurement. A set of this oxidation current and a reduction current for 1 minute was considered as one reverse current cycle, and the reverse current cycle was applied 10,000 times. After this, the overvoltage at a current density of -6kA / m2 was measured again, and this was taken as the overvoltage after the reverse current cycle test. [Table 2]
[0175] In the test (5), in each of the comparative examples 2-1 to 2-5, the cathode overvoltage increased by 50 mV or more after the test, whereas in each of the examples 2-1 to 2-18, the increase in overvoltage was suppressed to 30 mV or less, and it was found that the durability against 10,000 reverse current cycles was significantly higher. In addition, in Comparative Example 2-6, no electrolysis current was generated, and no hydrogen bubbles were generated due to electrolysis. This is believed to be because the oxide or hydroxide of element R present in the catalytic layer is an insulator or a conductor with a higher electrical resistance than metals, and therefore if the ratio of element R to Pt is too high, the electronic conductivity in the catalytic layer becomes significantly high. Furthermore, the initial overvoltage in Example 2-13 is higher than in Examples 2-1 to 2-12, and this is believed to be due to the fact that the ratio of element R to Pt is high, which reduces the electronic conductivity of the catalytic layer, for the same reason as above. These results demonstrate that a cathode having a catalytic layer containing Pt element and element R which is electrochemically stable as a trivalent ion within the potential window of water of pH 7 or more and pH 16 or less, in a molar ratio specified in the present invention, can maintain high energy conversion efficiency over a long period of time even in 200 pairs of alkaline water electrolysis cells including 199 bipolar electrolytic cells.
[0176] Comparing Examples 2-1 to 2-12 with Comparative Examples 2-1 to 2-5, the results in Test (5) were generally similar to those in Examples 1-1 to 1-12 and Comparative Examples 1-1 to 1-5 in Test (4). The reason why the overvoltage rise after 1,500 current interruptions in Comparative Examples 1 to 5 in Test (4) was larger than the overvoltage rise after 10,000 reverse current cycles in Comparative Examples 2-1 to 2-5 in Test (5) despite the smaller number of cycles is believed to be that in Test (4), the interruption time during which reverse current occurred was 5 minutes, whereas in Test (5), the time for which reverse current was applied was extremely short, on the order of several tens of seconds, and therefore the cathode damage per cycle was smaller in Test (5).
[0177] Comparing Examples 2-4 and 2-5 with Examples 2-1 to 2-3, Examples 2-4 and 2-5 had a smaller overvoltage rise in Test (5). This is believed to be because the cathodes 4 and 5 of Examples 2-4 and 2-5 contain the same Ni element as the conductive substrate in the first layer of the catalytic layer, improving the affinity between the catalytic layer and the conductive substrate, thereby suppressing peeling and falling off of the catalytic layer and the substrate due to reverse current.
[0178] In Example 2-18, the overvoltage after 10,000 reverse charging cycles is significantly lower than in Examples 2-1 to 2-20. After these tests, the cathodes were embedded in epoxy resin, and then processed by Ar ion beam (BIB processing) to prepare a cross section of the cathode. The BIB processed cross section was observed with an SEM (Hitachi High-Technologies Corporation S-4800) to obtain backscattered electron images (observation magnifications: 3000x, 10000x, 30000x). From this cross-sectional observation, it was found that the NiO layer present between the substrate Ni and the catalyst layer in Example 2-18 was significantly thinner than in Examples 2-1 to 2-17. This is thought to be because Pd has hydrogen molecule dissociation ability and hydrogen absorption ability, so hydrogen molecules generated by electrolysis are dissociated into atomic hydrogen and absorbed in the catalyst layer, and the reducing power of this atomic hydrogen suppresses the growth of the NiO layer due to the oxidation of the substrate Ni accompanying reverse charging. And because the NiO layer is an insulator and a conductor with higher electrical resistance than metals, it is believed that this growth inhibition contributed to suppressing the rise in overvoltage.
[0179] Next, Examples 3-1 and 3-2 and Comparative Examples 3-1 to 3-3 will be described.
[0180] (Example 3-1) A bipolar element was produced under the same conditions as in Example 1-1, except that a cathode 2 and an anode 4 produced as described below were used, and this was designated Example 3-1.
[0181] -Anode 4- A suspension was prepared by mixing and stirring 100 parts by mass of nickel oxide powder with a particle size of 0.2 to 2 μm, 2.25 parts by mass of gum arabic, 0.7 parts by mass of carboxymethylcellulose, 0.001 parts by mass of sodium lauryl sulfate, and 100 parts by mass of water. A granule with a particle size of 5 to 50 μm was prepared from the suspension by a spray drying method using a spray drying granulator.
[0182] As the Ni porous substrate, Ni expand metal with SW 3.0 mm, LW 4.5 mm, thickness 1.2 mm, and aperture ratio 54% was prepared and subjected to blasting treatment. The above granulated material was sprayed onto this Ni porous substrate by plasma spraying so that the projected area of the Ni porous substrate, not considering the holes, was 0.5 kg / m2 on each side, and the total of the front and back was 1.0 kg / m2. In the plasma spraying method, a gas in which argon and nitrogen were mixed at a ratio of 1:0.8 was used as the plasma gas. This electrode was placed in a quartz tube. This quartz tube was inserted into a tubular furnace, the inside of the quartz tube was heated to 200 ° C., and the catalyst layer was reduced by continuously supplying a hydrogen stream into the quartz tube. The Ni porous substrate on which the Ni catalyst layer was formed, which was produced by the above process, was used as the anode 4.
[0183] (Example 3-2) A bipolar element was produced under the same conditions as in Example 3-1 except that a cathode 4 was used, and this was designated as Example 3-2.
[0184] (Comparative Example 3-1) A bipolar element was produced under the same conditions as in Example 3-1, except that the cathode 101 was used, and this was designated as Comparative Example 3-1.
[0185] (Comparative Example 3-2) A bipolar element was produced under the same conditions as in Example 1-1, except that a cathode 107 and an anode 4 produced as described below were used, and this was designated Comparative Example 3-2. -Cathode 107- Coating solution 16 was prepared by mixing dinitrodiammine Pt nitric acid solution (Tanaka Precious Metals, Pt concentration: 100 g / L), Ce(III) nitrate hexahydrate (Kanto Chemical, Kaga special grade), and water so that the molar ratio of Pt element to Ce element was 75:25. A cathode 107 was produced under the same conditions as in Example 1-1, except that the cycle of the coating step, the precursor layer forming step, and the firing step was repeated 17 times using this coating liquid 16. The weight of the catalyst layer was then calculated assuming that the weight of the catalyst layer was the total weight of PtO and CeO2 contained in the catalyst layer.
[0186] (Comparative Example 3-3) A bipolar element was produced as Comparative Example 3-3 under the same conditions as in Example 1-1, except that a cathode 108 and an anode 4 produced as described below were used. -Cathode 108- Cathode 108 was produced under the same conditions as in Example 1-4, except that a cycle of the coating step and the precursor layer forming step was repeated five times using Coating Liquid 4 to form a first layer of the catalytic layer on the conductive base material, the weight of the first layer was calculated assuming that the weight of the first layer was the total weight of Pt and NiO contained in the first layer, and the weight of Pt contained in the first layer was calculated assuming that the weight of the second layer was the total weight of Pt and CeO2 contained in the catalytic layer.
[0187] The above-mentioned tests (1) to (3) and the following tests (6) and (7) were carried out for each of the examples and comparative examples. The results are shown in Table 3.
[0188] Test (6) Calculation of [IPt / (IPt+IPtO)] X-ray diffraction measurements were performed using a fully automated multipurpose X-ray diffraction instrument, SmartLab, manufactured by Rigaku Corporation. The sample was placed on a Si non-reflective sample plate to avoid background from the sample plate. To reduce X-rays from the sample, the sample was sized to be 2 cm square or larger, and the center of the sample was placed so that it coincided with the center of the X-ray beam. The height of the sample was then adjusted and measurements were performed. The measurements were performed using a Cu target as a rotating anode and CuKα radiation. The X-ray output was a tube voltage of 45 kV and a tube current of 200 mA. The optical arrangement was a reflective parallel optical system using a multilayer mirror on the incident side, and the incident side optical elements were a 2.5-degree solar slit and a 10 mm-wide vertical divergence slit, with a divergence slit width of 1 mm. The receiving side optical elements were a 0.5-degree PSA (Parallel Slit Analyzer) and a hybrid multidimensional pixel detector, HyPix-3000. The measurement was performed by the θ / 2θ method, which scans so that the angle between the sample surface and the X-ray source and the angle between the sample surface and the detector are constant, and the diffraction angle defined by 2θ was scanned in the range of 10 degrees to 90 degrees. The angle step was 0.05 degrees, and the scanning speed was 2 degrees / min, and an X-ray diffraction chart of the cathode in each example was obtained. The obtained X-ray diffraction chart was subjected to peak separation using the graph processing software "Igor Pro". Peak separation was performed in the angle range of 2θ = 25 degrees to 2θ = 42 degrees. After subtracting the background of the straight line connecting the measurement points at both ends of the angle, three Gaussian distribution functions with medians at (i) 30.0 to 36.0 degrees, (ii) 36.5 to 38.0 degrees, and (iii) 38.0 to 42.0 degrees were assumed, and peak separation was performed using the peak intensity, peak median, and full width at half maximum as parameters. Each peak is a combination of the contributions of CuKα1 and CuKα2, but they are not separated and are treated as the same peak. The three Gaussian distribution functions correspond to the reflections of (i) the (200) and (111) planes of PtO, (ii) the (111) plane of NiO, and (iii) the (111) plane of Pt metal, respectively. After the peak separation, the area of each peak was calculated, and the peak area of (iii) was designated as IPt, and the peak area of (i) was designated as IPtO, and [IPt / (IPt+IPtO)] was calculated.
[0189] Test (7) Bipolar electrolytic cell power-off cycle test 2 For each of the Examples and Comparative Examples, a bipolar electrolytic cell was prepared as follows, stacked in the order shown in Fig. 4. A bipolar electrolytic cell was constructed by stacking an anode terminal cell unit 51a using the anode described in each Example and Comparative Example, the diaphragm described above, a portion in which three sets of zero gap type bipolar elements of each Example and Comparative Example were stacked with the diaphragm sandwiched therebetween, the diaphragm described above, and a cathode terminal cell 51c using the cathode described in each Example and Comparative Example, in that order. Using this bipolar electrolytic cell, the electrolysis device shown in FIG. 3 was fabricated. The electrolysis device includes a bipolar electrolytic cell 50, a liquid feed pump 71 for circulating the electrolyte, and a gas-liquid separation tank 72 for separating the electrolyte from hydrogen and / or oxygen. The gas-liquid separation tank 72 and the bipolar electrolytic cell 50 are filled with an electrolyte that is a 30% KOH aqueous solution. The liquid feed pump 71 circulates the electrolyte through the anode chamber 5a of the bipolar electrolytic cell 50, the gas-liquid separation tank 72 for the anode, and the anode chamber 5a, and also through the cathode chamber 5c of the bipolar electrolytic cell 50, the gas-liquid separation tank 72 for the cathode, and the cathode chamber 5c. The temperature was adjusted to 90°C. In the electrolysis device, the gas separated in the gas-liquid separation tank 72 is recovered through a pressure gauge 78, a pressure control valve 80, and an oxygen concentration meter 75 or a hydrogen concentration meter 76. Furthermore, the power can be controlled by a rectifier 74. Furthermore, a flow meter 77 and a heat exchanger 79 are provided in the flow path of the circulating electrolyte. Furthermore, the arrows in Fig. 3 indicate the flow directions of the circulating liquid (electrolyte) and the gas. The electrolyte contact part of the circulation flow path was made of SGP carbon steel piping with Teflon (registered trademark) lining, and 20A piping was used. The gas-liquid separation tank 72 had a height of 1400 mm and a volume of 1 m 3 The following was used. The gas-liquid separation tank 72 has a height of 1400 mm and a volume of 1 m 3 The following items were used. The liquid volume in each gas-liquid separation tank 72 was set to about 50% of the design volume. In the external header type electrolytic cell, four external pipes (anode inlet header 10ai, cathode inlet header 10ci, anode outlet header 10ao, cathode outlet header 10co) for the electrolyte to flow are provided in the electrolysis frame that serves as the housing of the bipolar element. Each of these external pipes is connected to each electrode chamber of the electrolytic cell by an external hose. This piping structure is called the external header structure. The external header piping is divided into a cathode side external header piping and an anode side external header piping. Therefore, in each element, the electrolyte enters the cathode chamber 5c from the cathode inlet header 10ci through the external hose, and flows from the cathode chamber 5c to the cathode outlet header 10co through the external hose. Similarly, on the anode side, the electrolyte enters the anode chamber 5a from the anode inlet header 10ai through the external hose, and flows from the anode chamber 5a to the anode outlet header 10ao through the external hose. Since the inlet header of the external header is on the lower side of the electrolysis frame and the outlet header is on the upper side of the electrolysis frame, the electrolyte flows from the bottom to the top. It also rises in a direction approximately perpendicular to the electrode surface. A thermocouple is installed in the external hose of each cell, and the temperature difference before and after passing through the element can be measured. In this example, there are 29 anode chambers 5a and 29 cathode chambers 5c, and the structure is such that the electrolyte flows from the inlet header to the outlet header in each of the 29 chambers. In the cathode chamber 5c, hydrogen gas is generated by electrolysis, and in the anode chamber 5a, oxygen gas is generated, so that in the cathode outlet header 10co, a mixed phase flow of electrolyte and hydrogen gas is formed, and in the anode outlet header 10ao, a mixed phase flow of electrolyte and oxygen gas is formed. A current was applied from the rectifier 74 to the bipolar electrolytic cell 50 with respect to the areas of the cathode and anode under the conditions of Electrolysis Test 1 or Electrolysis Test 2 described below. The pressure inside the cell after the start of current application was measured with a pressure gauge 78, and the cathode side pressure was adjusted to 50 kPa and the oxygen side pressure to 49 kPa. The pressure was adjusted by a control valve 80 installed downstream of the pressure gauge 78. In the electrolysis device, the gas separated in the gas-liquid separation tank 72 is recovered through a pressure gauge 78, a pressure control valve 80, and an oxygen concentration meter 75 or a hydrogen concentration meter 76. Furthermore, the power can be controlled by a rectifier 74. Furthermore, a flow meter 77 and a heat exchanger 79 are provided in the flow path of the circulating electrolyte. The electrolysis apparatus for alkaline water electrolysis was produced using a rectifier, an oxygen concentration meter, a hydrogen concentration meter, a pressure gauge, a liquid delivery pump, a gas-liquid separation tank, a water supply unit, and the like that are all commonly used in the relevant technical fields.
[0190] When hydrogen generating electrolysis was performed using the above electrolysis apparatus, the potential of the zero gap type bipolar element was equal to the potential of the cathode, and the PTFE-coated Pt wire fixed near the cathode in the cathode chamber of the zero gap type bipolar element became an RHE electrode by contacting hydrogen generated by electrolysis and was at a hydrogen generating potential; therefore, the potential difference between the zero gap type bipolar element and the PTFE-coated Pt wire was measured, and this potential difference was taken as the cathode overvoltage. Using the above electrolysis device, the current density was 6 kA / m 2 Water electrolysis was performed continuously for 100 hours with positive current so that the electrolysis was stopped for 5 minutes. Then, the current was applied again at 6 kA / m 2 The positive current was applied for 5 minutes and then stopped for 5 minutes. Each of these 5 minutes of positive current application and 5 minutes of stoppage was counted as one current application / stop cycle, and 500 current application / stop cycles were performed. The average value of the cell voltages of the two cells not including the anode terminal cell unit 51a and the cathode terminal cell 51c during the first 5 minutes of positive current application after 100 hours of positive current application was defined as the initial cell voltage, the average value of the cathode overvoltages of the two cells described above at this time was defined as the initial overvoltage, and the average value of the cathode overvoltages of the two cells described above during the positive current application included in the 500th current application / stop cycle was defined as the post-test overvoltage.
[0191] [Table 3]
[0192] In the test (7), in each of the comparative examples 3-1 to 3-3, the cathode overvoltage increased by 150 mV or more after the test, whereas in each of the examples 3-1 to 3-3, the increase in overvoltage was suppressed to 10 mV or less, and it was found that the batteries exhibited significantly higher durability against 500 interruptions of current flow. These results demonstrate that a cathode having a catalyst layer containing Pt element and element R, which is electrochemically stable as a trivalent ion within the potential window of water from pH 7 to pH 16 inclusive, in the molar ratio specified by the present invention, has high durability.
[0193] Comparing Example 3-1 and Comparative Example 3-2, it is found that the durability against current interruption differs greatly depending on whether the catalyst layer contains Y or Ce. This is thought to be because Y is a trivalent ion that is electrochemically stable within the potential window of water from pH 7 to pH 16, while Ce undergoes oxidation-reduction reactions from trivalent to tetravalent and from tetravalent to trivalent within the potential window of water from pH 7 to pH 16. FIG. 8 shows the results of cyclic voltammetry of cathode 20 measured in 8M-KOH at 70° C. at a potential sweep rate of 100 mV / sec, and FIG. 9 shows the results of cyclic voltammetry of cathode 107 measured under similar conditions. In FIG. 9, a redox reaction is observed that does not exist in FIG. 8, which is paired with an oxidation peak near +0.77 V vs. RHE and a reduction peak near +0.56 V vs. RHE. With reference to Atlas of Electrochemical Equilibria in Aqueous Solutions (by Marcel Pourbaix, published by National Association of Corrosion Engineers, 1974), this redox reaction is considered to be a redox reaction between Ce3+ and Ce4+. Therefore, the chemical state of Ce in the cathode 107, which was applied with a positive current of 6 kA / m2 for 5 hours in a three-electrode cell, was analyzed by X-ray photoelectron spectroscopy. The electrode was cut into a size of about 3 mm × 20 mm and placed on a recess holder attached to the device. A molybdenum mask with a hole diameter of 5 mm was placed on top of it and the mask was fixed with a dedicated leaf spring and screw, and the sample was grounded. For the X-ray photoelectron spectroscopy measurement, an ULVAC-PHI VersaProbeII was used, and the measurement was performed under the following conditions: excitation source: monochromatic Al Kα 15 kV × 3.3 mA, analysis size: about 200 μmφ, pass energy: 23.5 eV (narrow scan), energy step: 0.1 eV, and charging correction: none. Figure 10 shows the analysis results of the cathode 107. Before the current was passed, the Ce in the cathode 107 contained a mixture of trivalent and tetravalent ions. However, after the current was passed, the tetravalent ions were predominant, indicating that a change in valence had occurred during the current pass. Furthermore, the surface of the cathode 107 was observed under SEM after the test (7). It was confirmed that the catalyst layer had fallen off significantly in the cathode 107. Furthermore, it was confirmed that the catalyst layer had broken into flakes in the areas where it barely remained. Figure 11 shows the surface (magnification 3000x) of the barely remaining catalyst layer of the cathode 107 after the test (7). From the above, it is believed that Ce undergoes trivalent to tetravalent and tetravalent to trivalent oxidation-reduction reactions within the potential window of water from pH 7 to pH 16, causing changes in the crystal morphology in the catalyst layer, which leads to the catalyst layer collapsing and peeling off from the substrate, resulting in low durability during current-stop cycles.In contrast, Y is electrochemically stable as a trivalent ion within the potential window of water from pH 7 to pH 16, and therefore exhibits high reverse current durability.
[0194] Comparing Examples 3-1 and 3-2, the overvoltage rise after the current-stop cycle test is suppressed in Example 3-2. This is believed to be due to the fact that the ratio of Pt element present as metal in the catalytic layer in the cathode 4 of Example 3-2 and its crystallinity are higher than those in the cathode 20 of Example 3-1. As shown by the comparison of [IPt / (IPt+IPtO)], it can be seen that Pt in the catalytic layer in the cathode 2 of Example 3-1 is mainly PtO amorphous, whereas Pt crystal is mainly in the cathode 4 of Example 3-2. PtO in the cathode catalytic layer is reduced to Pt metal crystal by electrolytic reduction accompanying positive current flow, but it is believed that by crystallizing it into Pt metal before electrolysis, the adhesion between the Pt crystal fine particles in the catalytic layer is improved and the depletion of the catalytic layer is suppressed. Although the mechanism is unclear, the inventors have confirmed that forming a catalyst layer containing Pt and Ni as the first layer and a catalyst layer containing Pt and the element R as the second layer promotes the growth of Pt metal crystals more than simply forming a catalyst layer containing Pt and the element R. From these results, it was found that when the peak area of the X-rays diffracted by the (111) plane of the Pt metal in the catalyst layer is IPt, and the peak area of the X-rays diffracted by the (200) and (111) planes of PtO is IPtO, it is more preferable that the value of [IPt / (IPt+IPtO)] is 0.1 or more. However, as shown in Comparative Example 3-1, even if the X-ray diffraction peak satisfies the above condition, this effect cannot be obtained unless the present invention contains in the catalyst layer an element R that is electrochemically stable as a trivalent ion within the potential window of water of pH 7 or more and pH 16 or less.
[0195] In addition, the initial cell voltage is low in Examples 3-1 and 3-2 compared to Examples 1-1 to 1-12. This is due to the effect of the anode, and the anodes 1 to 3 in Examples 1-1 to 1-12 do not form a catalyst layer, whereas the anode 4 in Examples 3-1 and 3-2 forms a catalyst layer. In general, when a catalyst layer is formed on the anode, the reverse current discharge amount increases, and the potential of the cathode is swept more noble by the reverse current caused by the current stop, and the deterioration due to the reverse current increases. Therefore, the cell voltage and durability are generally in a trade-off relationship. From this point of view, the significance of the present invention, which can obtain high current stop durability even when an anode with a catalyst layer is formed and a bipolar element is formed in order to further increase the energy efficiency of hydrogen production by electrolysis, is great.
[0196] Next, Examples 4-1 to 4-4 and Comparative Examples 4-1 to 4-3 will be described. (Example 4-1) A cathode 2 and an anode 4 were used in the same manner as in Example 3-1.
[0197] (Example 4-2) As in Example 3-2, a cathode 4 and an anode 4 were used.
[0198] (Example 4-2) As in Example 3-2, a cathode 4 and an anode 4 were used.
[0199] (Example 4-3) A cathode 17 and an anode 4 prepared as described below were used. -Cathode 17- A cathode 21 was produced under the same conditions as in Example 1-4, except that a cycle of the coating step and the precursor layer forming step was repeated twice using Coating Liquid 4 to form a first layer of the catalytic layer on the conductive base material, the weight of the first layer was calculated assuming that the weight of the first layer was the total weight of Pt and NiO contained in the first layer, and a cycle of the coating step and the precursor layer forming step was repeated 14 times using Coating Liquid 5 to form a second layer of the catalytic layer on the conductive base material on which the first layer was formed, and the weight of the second layer was calculated assuming that the weight of the second layer was the total weight of Pt and YO contained in the catalytic layer.
[0200] (Example 4-4) A cathode 18 and an anode 4 prepared as follows were used. -Cathode 18- Cathode 22 was produced under the same conditions as in Example 1-4, except that a cycle of the coating step and the precursor layer forming step was repeated 8 times using Coating Liquid 4 to form a first layer of the catalytic layer on the conductive base material, the weight of the first layer was calculated assuming that the weight of the first layer was the total weight of Pt and NiO contained in the first layer, and a cycle of the coating step and the precursor layer forming step was repeated 9 times using Coating Liquid 5 to form a second layer of the catalytic layer on the conductive base material on which the first layer was formed, and the weight of the second layer was calculated assuming that the weight of the second layer was the total weight of Pt and YO contained in the catalytic layer.
[0201] (Comparative Example 4-1) As in Comparative Example 3-1, a cathode 101 and an anode 4 were used.
[0202] (Comparative Example 4-2) As in Comparative Example 3-2, a cathode 107 and an anode 4 were used.
[0203] (Comparative Example 4-3) As in Comparative Example 3-3, a cathode 108 and an anode 4 were used.
[0204] For each of the Examples and Comparative Examples, the above-mentioned tests (1) to (3) and (6) and the following test (8) were carried out. The results are shown in Table 4.
[0205] Test (8) Reverse current cycle test 2 simulating a 200-pair bipolar electrolytic cell A reverse current cycle test was carried out simulating a 200-pair bipolar electrolytic cell using a three-electrode method with a potentiogalvanostat PARSTAT MC 1000 manufactured by Princeton Applied Research, as follows. First, in a 200-pair bipolar electrolytic cell, the average value of the reverse current flowing through each cell after electrolysis was stopped was calculated to be 15 A / m2 using an equivalent circuit. Next, discharge curves were obtained at the above current densities for the cathode and anode described in each of the examples and comparative examples. The cathode was cut to 18mm x 17mm and fixed to a PTFE-coated nickel rod with a nickel screw. A Pt mesh was used as the counter electrode, and a silver-silver chloride (Ag / AgCl) glass electrode was used as the reference electrode. The electrolyte was a 34 wt% aqueous potassium hydroxide solution. The temperature of the electrolyte was adjusted to 70°C. First, a reduction current with a current density of -6kA / m2 was applied for 1 hour, and then an oxidation current with a current density of +15A / m2 was immediately applied without any open circuit voltage measurement. At this time, the potential of the cathode gradually increased from the hydrogen generation potential to a more noble potential. When the potential of the cathode reached +1.25V (vs RHE), the current was stopped. The absolute value of the integrated current charge obtained from the product of the current density and the current application time was plotted on the horizontal axis, and the cathode potential on the vertical axis to obtain the cathode discharge curve. Next, the anode was cut to 18mm x 17mm and fixed to a PTFE-coated nickel rod with a nickel screw. A Pt mesh was used as the counter electrode, and a silver-silver chloride (Ag / AgCl) glass electrode was used as the reference electrode. The electrolyte was a 34 wt% potassium hydroxide aqueous solution. The temperature of this electrolyte was adjusted to 70°C. First, an oxidizing current with a current density of +6kA / m2 was applied for 1 hour, and then a reducing current with a current density of -15A / m2 was immediately applied without any open circuit voltage measurement. At this time, the potential of the anode gradually decreased from the oxygen generation potential to a more noble potential. When the potential of the anode reached +0.12V (vs RHE), the current was stopped. The absolute value of the integrated current charge obtained from the product of the current density and the current application time was plotted on the horizontal axis, and the potential of the anode was plotted on the vertical axis to obtain the discharge curve of the anode. The discharge curve of the cathode and the discharge curve of the anode were then superimposed, and the potential at which they intersected was set as the potential that the reverse current would reach when the current flow was stopped. An example is shown in Figure 12. Using the reverse current density obtained as above and the ultimate potential of the reverse current in each of the examples and comparative examples as conditions, a reverse current cycle test was carried out as follows. The cathode was cut to 18 mm x 17 mm and fixed to a PTFE-coated nickel rod with a nickel screw. A Pt mesh was used as the counter electrode, and a silver-silver chloride (Ag / AgCl) glass electrode was used as the reference electrode. The electrolyte was a 34 wt% aqueous potassium hydroxide solution. The temperature of this electrolyte was adjusted to 70°C. In this state, the overvoltage at a current density of -6kA / m2 was measured. At this time, the ohmic loss that could not be completely eliminated even by using the three-electrode method was measured by the AC impedance method, and the overvoltage was corrected based on the measured ohmic loss. Next, as a pretreatment of the cathode, a reduction current with a current density of -6kA / m2 was applied for 5 hours, and then an oxidation current of +15A / m2 was immediately applied without any open circuit voltage measurement or the like. At this time, the potential of the cathode gradually increases from the hydrogen generation potential to a noble potential. When the potential of the cathode reached the reverse current reach potential of each example, a reduction current of -6kA / m2 was immediately applied for 1 minute without any open circuit voltage measurement or the like. A set of this oxidation current and a reduction current for 1 minute was counted as one reverse current cycle, and the reverse current cycle was applied 2000 times. After this, the overvoltage at a current density of -6kA / m2 was measured again, and this was taken as the overvoltage after the reverse current cycle test.
[0206] [Table 4]
[0207] Comparing Examples 4-1 and 4-2 with Comparative Examples 4-1 to 4-3, the results in Test (8) were generally similar to those in Examples 3-1 and 3-2 and Comparative Examples 3-1 to 3-3 in Test (7). From these results and Examples 4-3 and 4-4, it was found that a cathode having a catalytic layer containing Pt element, in a molar ratio specified by the present invention, and element R that is electrochemically stable as a trivalent ion within the potential window of water of pH 7 or more and pH 16 or less, can maintain high energy conversion efficiency over a long period of time even in 200 pairs of alkaline water electrolysis cells including 199 bipolar electrolytic cells for alkaline water electrolysis, and that when the peak area of X-rays diffracted by the (111) plane of Pt metal in the catalytic layer is IPt, and the peak area of X-rays diffracted by the (200) and (111) planes of PtO is IPtO, it is more preferable that the value of [IPt / (IPt+IPtO)] is 0.1 or more. [Industrial Applicability]
[0208] According to the present invention, it is possible to provide a cathode for hydrogen generation that maintains high energy conversion efficiency for a long period of time without an increase in overvoltage even when hydrogen generation is started and stopped repeatedly. [Explanation of symbols]
[0209] 1 Bulkhead 2 electrodes 2a anode 2c cathode 2e Elastic body 2r Current collector 3 Outer Frame 4 Diaphragm 5 Electrode chamber 5a Anode chamber 5c cathode chamber 5i Electrolyte inlet 5o Electrolyte outlet 6. Ribs 7 Gasket 8 PFA-coated Pt wire 9a Nozzle 9b Cap nut 9c PTFE board 9d EPDM board 10. Header 10o External Header 10ai Anode Inlet Header 10ao Anode Outlet Header 10ci Cathode Inlet Header 10co cathode outlet header 50 bipolar electrolyzer 51g fast head, loose head 51i Insulating plate 51a Anode terminal element 51c Cathode Terminal Element 51r tie rod 60 Multi-pole element 65 Electrolysis Cell 70 Electrolyzer 71 Liquid delivery pump 72 Gas-liquid separation tank 74 Rectifier 75 Oxygen concentration meter 76 Hydrogen concentration meter 77 Flow meter 78 Pressure Gauge 79 Heat exchanger 80 Pressure Control Valve Z Zero gap structure
Claims
1. At least one of Pt, Pt oxide, and Pt hydroxide on a surface of a conductive substrate; At least one of a metal, an oxide, and a hydroxide of an element R selected from Sc or Y; A cathode for generating hydrogen having a catalyst layer containing A cathode for generating hydrogen, characterized in that the molar ratio of Pt element to element R (Pt:R) in the catalyst layer is 95:5 to 65:
35.
2. 2. The electrode according to claim 1, which is a cathode for alkaline water electrolysis.
3. 3. The cathode according to claim 1, wherein the catalyst layer contains the same type of element as that contained in the conductive base material.
4. 3. The cathode according to claim 1, wherein the catalytic layer comprises a first layer formed on the surface of the conductive base material and a second layer formed on the first layer, the first layer having a different molar ratio of Pt element to element R.
5. 5. The cathode of claim 4, wherein the molar ratio of element R in the second layer is greater than the molar ratio of element R in the first layer.
6. 6. The cathode according to claim 4, wherein the first layer contains the same type of element as that contained in the conductive base material.
7. 3. The cathode according to claim 1, wherein a peak area of X-rays diffracted by a (111) plane of Pt metal in the catalytic layer is IPt, and a peak area of X-rays diffracted by a (200) plane and a (111) plane of PtO is IPtO, where IPt / (IPt+IPtO) is a value of 0.1 or more.
8. 3. The cathode according to claim 1, wherein the element R is Y.
9. The cathode according to claim 1 or 2, characterized in that the conductive base material contains Ni.
10. 10. The cathode according to claim 9, wherein the conductive base material is a plain weave mesh made of Ni fine wires having a wire diameter of 0.05 mm to 1.00 mm woven at 20 meshes to 60 meshes.
11. The cathode according to claim 9, wherein the conductive substrate is a Ni foil having a thickness of 100 um or less.
12. The cathode according to any one of claims 9 to 11, wherein the catalyst layer contains Pt, Y and Ni.
13. 13. The cathode according to claim 12, wherein the catalyst layer comprises the first layer containing Pt and Ni and the second layer containing Pt and Y.
14. The loading amount of the catalyst layer is 4.5 g / m 2 20g / m or more 2 3. The cathode according to claim 1 or 2, characterized in that:
15. The amount of Pt element supported in the catalyst layer is 3.5 g / m 2 15g / m or more 2 3. The cathode according to claim 1 or 2, characterized in that:
16. 3. The cathode according to claim 1, wherein the catalyst layer contains a hydrogen storage alloy.
17. 17. The cathode according to claim 16, wherein the hydrogen storage alloy contains Pd.
18. 6kA / m 2 After applying a reduction current of 15 A / m for 1 hour, 2 The cumulative discharge amount until the potential reaches +1.12 V (vs. RHE) is 1500 C / m 2 More than 10000C / m 2 3. The cathode according to claim 1 or 2, characterized in that:
19. The electric double layer capacity is 0.01 F / cm 2 0.15F / cm or more 2 3. The cathode according to claim 1 or 2, characterized in that:
20. a coating step of coating the conductive substrate with a coating liquid containing at least a Pt compound and a compound of element R; a precursor layer forming step of drying the coating liquid to form a precursor layer containing Pt and an element R on the conductive base material; A calcination step of heating the precursor layer at a temperature range of 300° C. to 800° C. to obtain a catalyst layer. The method for producing a cathode according to claim 1 or 2, comprising the steps of repeating the steps in sequence two or more times.
21. A first coating step of coating the conductive base material with a first coating liquid containing at least a Pt compound and a compound of element R; a first precursor layer forming step of drying the first coating liquid to form a first precursor layer containing Pt and an element R on the conductive base material; a first firing step of heating the first precursor layer at a temperature in the range of 300° C. to 800° C. to obtain the first layer; After the first step is repeated two or more times in sequence, a second coating step of coating a second coating liquid containing at least a Pt compound and a compound of element R in a molar ratio different from that of the first layer on the conductive substrate on which the first layer is formed; a second precursor layer forming step of drying the second coating liquid to form a second precursor layer on the first layer, the second precursor layer containing Pt and the element R in a molar ratio different from that of the first layer; a second firing step of heating the second precursor layer at a temperature in the range of 300° C. to 800° C. to obtain a second layer; The method for producing a cathode according to claim 4, further comprising repeating the second step two or more times in sequence.
22. A first coating step of coating the conductive base material containing Ni with a first coating liquid containing at least a Pt compound and Ni; a first precursor layer forming step of drying the first coating liquid to form a first precursor layer containing Pt and Ni on the conductive base material; a first firing step of heating the first precursor layer at a temperature in the range of 300° C. to 800° C. to obtain the first layer; After the first step is repeated two or more times in sequence, a second coating step of coating a second coating liquid containing at least a Pt compound and a Y compound on the conductive base material on which the first layer has been formed; a second precursor layer forming step of drying the second coating liquid to form a second precursor layer containing Pt and Y on the first coating layer; a second firing step of heating the second precursor layer at a temperature in the range of 300° C. to 800° C. to obtain a second layer; The method for producing a cathode according to claim 13, further comprising repeating the second step two or more times in sequence.
23. A bipolar electrolytic cell comprising the cathode according to claim 1 or 2.
24. The cathode and the anode are provided, 6 kA / m 2 After passing an oxidation current of 15 A / m for 1 hour, 2 The cumulative discharge amount until the potential reaches +0.12 V (vs. RHE) is 6 kA / m 2 After applying a reduction current of 15 A / m for 1 hour, 2 24. The bipolar electrolytic cell according to claim 23, wherein the accumulated discharge amount is greater than an accumulated discharge amount until the potential reaches +1.12 V (vs. RHE) when an oxidation current of 1.0 V is passed through the bipolar electrolytic cell.
25. 6 kA / m 2 After passing an oxidation current of 15 A / m for 1 hour, 2 The cumulative discharge amount until the potential reaches +0.12 V (vs. RHE) is 10,000 C / m 2 More than 300000C / m 2 25. The bipolar electrolytic cell of claim 24, wherein:
26. 26. The bipolar electrolytic cell of claim 25, wherein the anode comprises Ni.
27. 3 to 200 bipolar electrolytic cells according to claim 26; At least one cathode terminal cell; At least one anode terminal cell; An electrolytic cell for alkaline water electrolysis comprising:
28. A method for producing hydrogen, comprising electrolyzing alkali-containing water using the alkaline water electrolysis cell according to claim 27 to produce hydrogen.
29. 29. The method for producing hydrogen according to claim 28, wherein hydrogen is produced by electrolyzing water containing an alkali using a variable power supply that includes repeated switching between positive current application and the cessation of positive current application.
Citation Information
Patent Citations
Burner for liquid fuel combustion equipment
JP1980053605A
Electrode for hydrogen generation, process for producing same, and method of electrolysis therewith
WO2015098058A1